Zirconium-rich Cr-Zr-N alloy coating, film-coated product, application of zirconium-rich Cr-Zr-N alloy coating in hard coating and preparation method

The zirconium-rich Cr-Zr-N alloy coating addresses the challenge of achieving high hardness and corrosion resistance by optimizing the atomic ratio and structure, resulting in a dense, scratch-resistant, and corrosion-resistant coating.

CN119177424APending Publication Date: 2024-12-24VITALINK INDUSTRY (SHENZHEN) CO LTD

Patent Information

Application Number
CN202310746573.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing alloy nitride coatings struggle to simultaneously achieve high hardness and high corrosion resistance due to internal stress and defects during the coating growth process.

Method used

A zirconium-rich Cr-Zr-N alloy coating with a specific atomic ratio (Cr x Zr y N z ) is developed, featuring a highly disordered atomic distribution and dense structure, which enhances hardness and corrosion resistance.

Benefits of technology

The Cr-Zr-N alloy coating provides both high hardness and excellent corrosion resistance, effectively resisting scratches and corrosion while maintaining a dense structure to prevent penetration of corrosive media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177424A_ABST
    Figure CN119177424A_ABST
Patent Text Reader

Abstract

The invention relates to a zirconium-rich Cr-Zr-N alloy coating, a coated product, application and a preparation method. The Cr-Zr-N alloy coating contains a Cr-Zr-N alloy material with the chemical formula of (CrxZryNz) Ma, M is a doping element, x, y, z and a are respectively and independently atomic ratios, 15.0 < = x < = 53.8, 30.0 < = y < = 78.8, 6.2 < = z < = 35.5, and 0 < = a / (x + y + z + a) < = 0.05. The zirconium-rich Cr-Zr-N alloy coating has high content of zirconium, has high hardness and excellent corrosion resistance by optimizing the proportion of three elements, and can be used as at least one part of a hard coating in a coated product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy coatings, and further to the technical field of zirconium-containing coatings, and in particular to zirconium-rich Cr-Zr-N alloy coatings, plated products, applications in hard coatings, and preparation methods. Background Art

[0002] With the rapid development of modern science and technology, hard coatings have emerged to improve the surface properties of various materials and parts. Hard coatings have high hardness and play an increasingly important role in 3C digital products, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace and other fields.

[0003] Metal nitrides generally have the characteristics of high melting point and hardness, good thermal stability, and excellent oxidation resistance. Nitrides of transition metals such as titanium, chromium, vanadium, niobium, zirconium, and hafnium are usually used as strengthening coatings on the surface of cutting tools to increase hardness. The most common, earliest studied, and most widely used are titanium nitride coatings (TiN coatings) and chromium nitride coatings (CrN coatings). Among them, TiN coatings have the advantages of high hardness, good toughness, good chemical stability, and gorgeous color. They have been successfully applied in the tool industry and have been hailed as "a revolution in tools." In addition to being used as functional coatings, TiN coatings can also be used as decorative coatings; compared with TiN coatings, CrN coatings have lower friction coefficients, better high temperature resistance and corrosion resistance, and higher sputtering yields, which are conducive to large-scale industrial production. In addition, the internal stress of CrN coatings is lower, resulting in lower hardness values ​​than TiN coatings.

[0004] With the widespread application of coating products, coating substrates have entered the era of light alloys, such as aluminum alloys. However, these light alloy materials have weak corrosion resistance. Therefore, new requirements are put forward for the corrosion resistance of hard coatings, requiring the protective coating on the surface of the substrate to have not only high hardness characteristics, but also excellent corrosion resistance. However, for traditional single metal nitride coatings, due to the large internal stress of the coating and defects during the coating growth process, although it has high hardness characteristics, it has poor corrosion resistance. In view of this, the research and development of alloy nitride coatings is timely.

[0005] However, existing alloy nitride coatings usually have difficulty in simultaneously meeting the requirements of high hardness and high corrosion resistance. Summary of the invention

[0006] Based on this, the purpose of the present invention includes providing a zirconium-rich Cr-Zr-N alloy coating, in which the Cr-Zr-N alloy material is rich in zirconium. The Cr-Zr-N alloy coating not only has high hardness but also has excellent corrosion resistance, and can be used as a protective coating or a part thereof for a coated product.

[0007] In a first aspect of the present invention, a zirconium-rich Cr-Zr-N alloy coating is provided, wherein the Cr-Zr-N alloy coating contains a Cr-Zr-N alloy material, wherein the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5, and 0≤a / (x+y+z+a)≤0.05.

[0008] In some embodiments, 64.5-y≤x≤93.8-y and 15.0≤x≤1.93y-23.4.

[0009] In some embodiments, 15.0≤x≤53.8, 33.7≤y≤78.8 and 6.2≤z<28.0. In some of these embodiments, 72-y<x≤93.8-y and 15.0≤x<2.5y-44.6.

[0010] In some embodiments, based on any suitable embodiment above, the sum of x, y and z is 100.

[0011] In some embodiments, based on any of the foregoing suitable embodiments, the Cr—Zr—N alloy coating satisfies the following two characteristics:

[0012] The X-ray diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;

[0013] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies

[0014] In some embodiments, based on any of the above suitable embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10nm to 50nm.

[0015] In some embodiments, d minIt is 10nm, 20nm, 25nm, 30nm, 40nm or 50nm.

[0016] In some embodiments, based on any of the foregoing suitable embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof;

[0017] The non-metallic elements include one or more of O, C, B, Si and Ar;

[0018] The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0019] In some embodiments, 0≤a / (x+y+z+a)≤0.02.

[0020] In a second aspect of the present invention, a coated product is provided, comprising a substrate and the Cr—Zr—N alloy coating according to the first aspect of the present invention; wherein the Cr—Zr—N alloy coating is located on at least one side of the substrate.

[0021] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material;

[0022] The material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based;

[0023] The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium;

[0024] The inorganic non-metallic material includes one or more of ceramics and glass.

[0025] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys;

[0026] The light alloy includes one or more of a titanium alloy, an aluminum alloy and a magnesium alloy.

[0027] In some embodiments, the coated product satisfies one or more of the following characteristics:

[0028] The Cr-Zr-N alloy coating is in direct contact with the substrate or is provided with a transition layer;

[0029] The Cr-Zr-N alloy coating is located on the surface of the coated product or a surface layer is further provided on the side of the Cr-Zr-N alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.

[0030] In the third aspect of the present invention, there is provided the use of the Cr-Zr-N alloy coating described in the first aspect of the present invention as at least a part of a hard coating, or the use of the coated product described in the second aspect of the present invention in the preparation of a product having a hard coating.

[0031] In some embodiments, the hard coating is also a corrosion resistant coating.

[0032] In a fourth aspect of the present invention, a method for preparing a Cr-Zr-N alloy coating is provided, comprising the following steps: using a vapor deposition technique to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of a substrate according to a preset atomic ratio, thereby forming the Cr-Zr-N alloy coating described in the first aspect of the present invention.

[0033] In some embodiments, the method for preparing the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using one or more targets comprising chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.

[0034] In some embodiments, the preparation method meets one or more of the following characteristics:

[0035] The temperature of sputtering deposition is 30℃~330℃;

[0036] The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3Pa to 1.2Pa;

[0037] The target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 ;

[0038] The target material includes a zirconium target, and the power density of the zirconium target is 0.8 W / cm 2 ~7.9W / cm 2 ;

[0039] The target material includes an alloy target, and the alloy target includes at least two metal elements in the Cr-Zr-N alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 ;

[0040] The bias voltage of the substrate is -150V to -20V;

[0041] The sputtering deposition time is 10min to 150min;

[0042] The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 8 sccm to 52 sccm;

[0043] The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon and nitrogen in the mixed gas is (2-6):1.

[0044] In a fifth aspect of the present invention, a Cr—Zr—N alloy material is provided, wherein the Cr—Zr—N alloy material is as defined in the first aspect of the present invention.

[0045] In the zirconium-rich Cr-Zr-N alloy coating provided by the present invention, the Cr-Zr-N alloy material mainly comprises three elements: Cr, Zr and N, and these three elements have a specific relative atomic ratio (Cr x Zr y N z ), 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5. The Cr-Zr-N alloy coating has a highly disordered atomic distribution and a sufficiently dense atomic arrangement based on the aforementioned zirconium-rich chemical composition. The coating has a dense structure, and thus has high hardness characteristics and excellent scratch resistance, which can reduce scratches or weaken scratch damage. In addition, the special structure of the Cr-Zr-N alloy coating also reduces or avoids the penetrating column gaps in traditional hard coatings, thereby greatly improving the corrosion resistance of the Cr-Zr-N alloy coating. The Cr-Zr-N alloy coating provided by the present invention has both high hardness and excellent corrosion resistance.

[0046] In the plated product, the position of the Cr-Zr-N alloy coating provided by the present invention can be flexibly set, and can directly contact the substrate or not directly contact the substrate, can be used as a surface layer, or can be located between the surface layers of the substrate and other structures and used as an intermediate film layer. The Cr-Zr-N alloy coating of the present invention in different positions can effectively resist scratches and scrapes while also providing excellent corrosion resistance. When the Cr-Zr-N alloy coating provided by the present invention is used on the surface of the plated product, it can provide a high-brightness surface, so that the coating has both beautiful decoration and protective effects.

[0047] The Cr-Zr-N alloy coating provided by the present invention can be used as at least a part of a hard coating, and can be used as a surface film layer, an intermediate film layer or a bottom film layer of the hard coating. The aforementioned coated product can be an intermediate product or a final product, and various products with a hard coating can be further prepared. The hard coating not only has high hardness characteristics, but can also provide excellent corrosion resistance as a corrosion-resistant coating.

[0048] The Cr-Zr-N alloy coating provided by the present invention can be applied to a variety of substrates, and the materials of the substrates include but are not limited to alloys, elemental metals, inorganic non-metallic materials (such as silicon wafers, ceramics, glass) and other substrates.

[0049] The preparation method of the Cr-Zr-N alloy coating provided by the invention is simple, easy to operate, green and environmentally friendly, and also has the advantages of being quantifiable, highly efficient and highly repeatable, and is suitable for industrial application.

[0050] The Cr-Zr-N alloy coating provided by the present invention can have both high hardness characteristics and excellent corrosion resistance in a relatively thin thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. It should also be noted that the drawings are all drawn in a simplified form and are only used to conveniently and clearly assist in explaining the present invention. The various sizes of each component shown in the drawings are arbitrarily shown and may be accurate or may not be drawn according to the actual scale. For example, in order to make the illustration clearer, the size of the components is appropriately exaggerated in some places in the drawings. Unless otherwise specified, the components in the figure are not drawn to scale. The present invention does not limit each size of each component.

[0052] In the following description, the same reference numerals denote the same parts.

[0053] Figure 1 It is a schematic structural diagram of a coated product including a zirconium-rich Cr-Zr-N alloy coating in one embodiment of the present invention, including a substrate and the Cr-Zr-N alloy coating of the present application;

[0054] Figure 2 Schematic diagrams of the structures of several coated products in several embodiments of the present invention: (A) includes a substrate, a transition layer and the Cr-Zr-N alloy coating of the present invention; (B) includes a substrate, a transition layer, the Cr-Zr-N alloy coating of the present invention and a surface layer; (C) includes a substrate, the Cr-Zr-N alloy coating of the present invention and a surface layer;

[0055] Figure 3 This is a schematic diagram of a device for preparing the Cr-Zr-N alloy coating of the present application in one embodiment of the present invention;

[0056] Figure 4 The Cr prepared in Example 1 of the present invention 53.8 Zr 40.0 N 6.2 SEM cross-sectional image of the alloy coating;

[0057] Figure 5 The Cr prepared in Example 1 of the present invention 53.8 Zr 40.0 N 6.2 XRD diffraction pattern (A), selected area electron diffraction pattern (B) and radial intensity profile (C) of the alloy coating;

[0058] Figure 6 The Cr prepared in Example 2 of the present invention 34.5 Zr 30.0 N 35.5 SEM cross-sectional image of the alloy coating;

[0059] Figure 7 The Cr prepared in Example 2 of the present invention 34.5 Zr 30.0 N 35.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0060] Figure 8 The Cr prepared in Example 3 of the present invention 15.0 Zr 78.8 N 6.2 SEM cross-sectional image (A), selected area electron diffraction pattern (SAED) image (B), and radial intensity profile corresponding to SEAD image (C) of the alloy coating;

[0061] Fig. 9 The Cr prepared in Example 4 of the present invention 15.0 Zr 49.5 N 35.5 SEM cross-sectional image of the alloy coating;

[0062] Fig.10 The Cr prepared in Example 4 of the present invention 15.0 Zr 49.5 N 35.5 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0063] Fig.11 The Cr prepared in Example 5 of the present invention 29.7 Zr 50.1 N 20.2 SEM cross-sectional image of the alloy coating;

[0064] Fig.12 The Cr prepared in Example 5 of the present invention 29.7 Zr 50.1 N 20.2 XRD diffraction pattern of alloy coating;

[0065] Fig.13 The Cr prepared in Comparative Example 1 of the present invention 88.9 Zr 11.1 SEM cross-sectional image of the alloy coating;

[0066] Fig.14 The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46 SEM cross-sectional image of the alloy coating;

[0067] Fig.15 The Cr prepared in Comparative Example 2 of the present invention 37.8 Zr 16.2 N 46 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0068] Fig.16 The Cr prepared in Comparative Example 4 of the present invention 39.6 Zr 19.4 N 41 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating.

[0069] In the XRD diffraction pattern, the horizontal axis is 2θ, the unit is °, and the vertical axis is the X-ray diffraction intensity (intensity), the unit is au; according to the selected area electron diffraction pattern (SAED) of the alloy coating, the corresponding radial intensity profile is obtained, which is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal axis, the unit is angstrom The vertical axis is the electron diffraction intensity (intensity), and the unit is au.

[0070] In the XRD diffraction pattern and the radial intensity profile corresponding to the SAED pattern, au has a well-known meaning in the art.

[0071] In some SEM images, when preparing the cross-section samples to be tested, some cross-section delamination occurs when the silicon wafer is brittle, but it does not affect the observation and analysis of the cross-section morphology. The positions of different structural layers in the substrate and protective coating can be determined according to the thickness of the corresponding structural layers.

[0072] Description of reference numerals: 1 is a vacuum chamber, 2 is a sample stage, 3 is a DC anode, 4 is a chromium target (also referred to as a Cr target, specifically a Cr target with radio frequency-assisted DC cathode power generation), and 5 is a zirconium target (also referred to as a Zr target, specifically a Zr target with radio frequency-assisted DC cathode power generation);

[0073] 100 is a substrate, 200 is a transition layer (also called a transition film layer), 300 is the Cr-Zr-N alloy coating of the present application, and 400 is a surface layer (also called a surface film layer). DETAILED DESCRIPTION

[0074] The present invention will be further described in detail below in conjunction with the accompanying drawings, embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive. It should also be understood that the present invention can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. For example, the features described or described as part of an embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present invention. It should be understood that the present invention can be implemented without one or more of these details.

[0075] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing implementation modes and embodiments and are not intended to limit the present invention.

[0076] the term

[0077] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0078] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, which include any combination of any two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".

[0079] In the present invention, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0080] In the present invention, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.

[0081] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.

[0082] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of the present invention, solve the technical problem of the present invention, and achieve the expected technical effect of the present invention.

[0083] Herein, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0084] In the present invention, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the contents covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of the present invention. In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0085] In the present invention, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist.

[0086] In the present invention, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0087] As used herein, the terms "comprising", "including" and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps.

[0088] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0089] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0090] In this article, unless otherwise specified, "about" means within a certain range above or below the number, and the fluctuation range may vary depending on the type and value of the number. For example, fluctuations within the range of ±2%, ±1%, ±0.5%, etc. of the number are allowed. For example, about 2° can be selected from 2°±0.02°, etc.

[0091] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0092] In the present invention, the term "room temperature" generally refers to 4°C to 35°C, such as 20°C ± 5°C. In some embodiments of the present invention, "room temperature" refers to 10°C to 30°C. In some embodiments of the present invention, "room temperature" refers to 20°C to 30°C.

[0093] In the present invention, the term "normal temperature" generally refers to 20°C to 35°C, for example, 20°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C.

[0094] In the present invention, when it comes to the unit of the data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3-5h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0095] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as a reference separately. Unless they conflict with the invention purpose and / or technical solution of the present application, the cited documents involved in the present invention are cited with all contents and all purposes. When the present invention involves cited documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the present invention involves cited documents, the examples and preferred embodiments of the cited relevant technical features may also be incorporated into this application as references, but are limited to the ability to implement the present invention. It should be understood that when the content of the citation conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0096] The mass or weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass or weight described in the description of the embodiments of the present invention may be units known in the chemical industry such as μg, mg, g, and kg.

[0097] In the present invention, if there are multiple steps involved in the method flow, unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0098] When describing positional relationships, unless otherwise specified, when an element such as a layer, film, or substrate is referred to as being "on" another film layer, it can be directly on the other film layer or there can be an intermediate film layer. Further, when a layer is referred to as being "under" another layer, it can be directly below or there can be one or more intermediate layers. It is also understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there can be one or more intermediate layers.

[0099] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0100] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0101] In order to improve the hardness of the coating, traditional alloy coatings mostly use nitrogen-rich alloy nitride coatings. Alloy nitride coatings mainly use different metal element components to form coatings with different microstructures to achieve different functional characteristics. Traditional alloy coatings mostly use nitrogen-rich designs to improve the hardness of the coating, and the atomic percentage of nitrogen is usually higher than 40%. In addition, in order to improve the hardness, although traditional multi-element alloy coatings also involve zirconium doping, which can improve the hardness to a certain extent, however, because zirconium is a large-sized atom, its metal activity is higher than titanium, and its price is higher than titanium, so titanium is generally used to replace zirconium in alloy research and development. The zirconium content in traditional alloys is usually not high, generally less than 10%.

[0102] The inventors of the present application have found through extensive research and experimental analysis that traditional hard coatings (such as TiN, etc.) are prone to forming columnar crystals during the nucleation and crystallization growth process, and usually have a columnar crystal structure. Moreover, a high content of columnar crystals will promote the formation of a highly ordered structure arranged in a directional manner. In the highly ordered structure, there are a large number of crystals that cause inter-crystal gap defects, which are mainly manifested as penetrating column gaps. There are shadows between the columnar crystals in the corresponding scanning electron microscope (SEM) cross-sectional diagram, and it is speculated that these penetrating column gaps may cause the alloy coating to be insufficiently dense. The inventors of the present application speculate that the traditional directional ordered structure is prone to cause the coating to be insufficiently dense, thereby limiting the hardness improvement; on the other hand, under corrosive conditions, the corrosive medium can quickly penetrate the coating through the penetrating gaps and react with the substrate, resulting in the corrosion resistance of the alloy coating being less than ideal.

[0103] In addition, the alloy materials on the market are mainly protected by means of anodic oxidation, magnetron sputtering, etc. For example, aluminum alloy is mainly protected by anodic oxidation, and its working principle is: the aluminum alloy material is placed in a strong acid or strong alkali solution to form oxides and metal and alloy coatings on the surface to form surface protection; because the solution is a strong acid or strong alkali, the hardness of the product formed by this method is relatively low. In addition, a large amount of wastewater, waste liquid and waste gas are generated during the production process, which is not conducive to environmental protection.

[0104] This application adopts a zirconium-rich alloy design and selects the element composition and ratio to form a new type of alloy nitride coating with a high zirconium content, specifically a Cr-Zr-N alloy coating. The alloy coating realizes a new alloy function: the zirconium-rich Cr-Zr-N alloy coating provided by the present invention not only has a high hardness characteristic, but also gives the alloy coating excellent corrosion resistance far higher than traditional hard coatings. It is a hard coating with excellent corrosion resistance and high hardness.

[0105] In a first aspect of the present invention, a zirconium-rich Cr-Zr-N alloy coating is provided, wherein the alloy material contained in the Cr-Zr-N alloy coating mainly contains three elements: Cr, Zr and N, and Cr, Zr and N have a specific relative atomic ratio (Cr x Zr y N z ), 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5, the zirconium-rich Cr-Zr-N alloy coating has a high content of zirconium, and through the optimization of the ratio of the three elements, it has both high hardness and excellent corrosion resistance, and can be used as at least a part of the hard coating in the plated product.

[0106] In some embodiments, a zirconium-rich Cr-Zr-N alloy coating is provided, wherein the Cr-Zr-N alloy coating contains a Cr-Zr-N alloy material, and the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , wherein x, y and z are each independently an atomic ratio, 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5, M is a doping element, a is the atomic ratio of the M element, and a is 0 or a positive number.

[0107] In some embodiments, a zirconium-rich Cr-Zr-N alloy coating is provided, wherein the Cr-Zr-N alloy coating contains a Cr-Zr-N alloy material, and the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a , wherein x, y and z are each independently an atomic ratio, 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5, M is a doping element, a is the atomic ratio of the M element, and 0≤a / (x+y+z+a)≤0.05.

[0108] The Cr-Zr-N alloy coating provided by the present invention can also be recorded as "Cr-Zr-N alloy coating of this application", "Cr-Zr-N alloy coating of this application", "Cr-Zr-N alloy coating described in this application", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating provided in this application" or "Cr-Zr-N alloy coating described in the present invention", and includes but is not limited to the Cr-Zr-N alloy coating provided in the first aspect.

[0109] In the present invention, unless otherwise specified, "Cr-Zr-N alloy" and "CrZrN alloy" both refer to alloys containing Cr, Zr and N elements, and other alloying elements may be contained, and the two can be used interchangeably.

[0110] In the present invention, unless otherwise specified, "Cr-Zr-N alloy material" refers to an alloy material containing Cr, Zr and N elements. Among them, in the Cr-Zr-N alloy material involved in the present invention, the three elements Cr, Zr and N have the above-mentioned specific atomic ratio x:y:z. In the present invention, the form of the Cr-Zr-N alloy material is not particularly limited, and can be, but not limited to, an alloy coating form.

[0111] In the present invention, unless otherwise specified, the "atomic ratio" of two or more elements means the atomic number ratio.

[0112] In the present invention, unless otherwise specified, "Cr-Zr-N ternary alloy" and "CrZrN ternary alloy" both refer to an alloy composed of three elements: Cr element, Zr element and N element.

[0113] In the zirconium-rich Cr-Zr-N alloy coating provided by the present invention, the Cr-Zr-N alloy material mainly comprises three elements: Cr, Zr and N, and these three elements have a specific relative atomic ratio of Cr: x Zr y N z , 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5. The Cr-Zr-N alloy coating has a highly disordered atomic distribution and a sufficiently dense atomic arrangement based on the aforementioned zirconium-rich chemical composition. The coating has a dense structure and thus has high hardness characteristics and excellent scratch resistance, which can reduce scratches or weaken scratch damage. In addition, the special structure of the Cr-Zr-N alloy coating also reduces or avoids the penetrating column gaps in traditional hard coatings, thereby greatly improving the corrosion resistance of the Cr-Zr-N alloy coating. The Cr-Zr-N alloy coating provided by the present invention has both high hardness and excellent corrosion resistance.

[0114] Since zirconium is a large-sized atom, its atomic activity is high and it is easy to alloy and nitridate, and its nitride or alloy nitride will show higher hardness. This application increases the element content of zirconium in the alloy coating, on the one hand, effectively improving the hardness of the alloy coating, and on the other hand, forming a specific atomic ratio with the Cr and N elements in the Cr-Zr-N alloy material, which can form a highly disordered atomic distribution and a fully dense atomic arrangement during the deposition process of the coating, further improving the hardness of the coating, and reducing or avoiding penetrating column cracks, significantly improving the corrosion resistance of the alloy coating.

[0115] High-hardness coatings have the effects of high hardness, low friction coefficient and wear resistance. When applied to substrates, such as metal substrates and alloy substrates, high hardness can be achieved, so that the coating has extremely strong high hardness and wear resistance. It is particularly suitable for 3C digital products, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace, tool surfaces and other fields that have high requirements for hardness and are easy to wear. For example, in the field of portable 3C products, such as the shell parts of mobile phones, they often rub against desktops, pockets, etc., which requires the surface of the shell to be protected by a high-hardness coating to increase the service life of the product. For example, in the field of molds and tools, by adding a high-hardness alloy coating, the wear resistance of the mold or tool can be effectively increased, and the durability of the alloy tool can also be extended. For another example, in the field of aerospace, the device shell forms overheating friction with the air during extremely high-speed operation and is very likely to cause wear. By adding a high-hardness alloy coating on the surface of the shell, friction and wear can be reduced, and the service life of the shell can be increased.

[0116] Corrosion-resistant coatings must be inherently inert and fully isolated. "Inherently inert" means that the coating material is sufficiently inert and not prone to chemical reactions with the corrosive media in the service environment. "Full isolation" means that the coating structure is dense enough to fully isolate the substrate from the service environment, preventing or delaying the reaction between the substrate and the corrosive media therein, thereby achieving the purpose of corrosion resistance.

[0117] Traditional hard coatings are usually nanocrystalline and have a high content of columnar crystals. The coatings usually have a large number of through pores, which on the one hand reduce the density of the coating and affect the hardness characteristics, and on the other hand lead to poor corrosion resistance.

[0118] The Cr-Zr-N alloy coating provided by the present invention has a characteristic structure of "highly disordered and fully densely packed", contains a very small amount of through-holes or no through-holes, and has a dense coating structure. Among them, the three atoms of Cr, Zr, and N with different radii have a special atomic ratio, which is conducive to making the atoms condense into a highly disordered state during deposition, and then densely stacked in a highly disordered state. The dual characteristics of "highly disordered distribution" and "fully densely packed arrangement" of atoms in the coating make the alloy coating easy to grow densely and improve the hardness of the coating, and can also inhibit the formation of a large number of continuous through-holes, thereby forming an effective isolation between the substrate and the corrosive environment, and significantly improving the corrosion resistance. In addition, a higher Zr content is also conducive to improving the chemical inertness of the coating itself in a corrosive environment, so that multiple factors synergistically and preferably improve the corrosion resistance of the Cr-Zr-N coating of the present invention.

[0119] In the Cr-Zr-N alloy coating of the present invention, based on the special atomic ratio of Cr, Zr and N, Cr and N are introduced to form a zirconium-rich Cr-Zr-N alloy coating with a high content of Zr, which not only makes it easy for Cr and Zr to form a strong bond energy, but also facilitates the rapid growth of a Cr-Zr alloy with a suitable atomic ratio during the deposition process. In addition, the addition of an appropriate amount of nitrogen further promotes the re-nucleation of the Cr-Zr alloy to form the Cr-Zr-N alloy of the present invention, and improves the coating hardness and corrosion resistance by improving the density of the coating nucleation. Among them, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The atomic sizes of Cr and Zr are close, while the atomic size of N is smaller. During the nucleation process, an appropriate amount of small-sized N atoms can penetrate into the pores of large-sized Cr and Zr metal grains with appropriate atomic ratios, achieving a better pore-filling effect and making the atomic arrangement denser. At the same time, it can inhibit the growth defects of the columnar crystal structure of the film, thereby better improving the hardness and corrosion resistance of the coating.

[0120] In some embodiments, 64.5-y≤x≤93.8-y and 15.0≤x≤1.93y-23.4. At this time, the three elements of Cr, Zr and N can form a better synergistic effect, which is more conducive to improving the excellent comprehensive performance of high hardness and high corrosion resistance of the alloy coating.

[0121] In some embodiments, 15.0≤x≤53.8, 33.7≤y≤78.8 and 6.2≤z<28.0, further, the following formula 72-y<x≤93.8-y and 15.0≤x<2.5y-44.6 may be satisfied. The atomic ratio of Cr, Zr and N at this time is conducive to forming a denser, higher hardness and higher corrosion resistant alloy coating.

[0122] In some embodiments, based on any suitable embodiment described above, the sum of x, y and z is 100. At this time, x, y and z correspond to the atomic percentages of the three elements Cr, Zr and N, respectively. At this time, the ratio of the three atoms of Cr, Zr and N is constrained within a more suitable range, so that the formed Cr-Zr-N alloy coating is conducive to obtaining a denser structure, and is conducive to achieving a higher coating hardness and better corrosion resistance.

[0123] In some embodiments, when the proportion relationship of 15.0≤x≤53.8, 30.0≤y≤78.8 and 6.2≤z≤35.5 is satisfied and x+y+z=100, x can be any of the following values ​​or an interval consisting of any two of the following values: 15.0, 20.0, 25.0, 29.7, 30.0, 34.5, 35.0, 40.0, 41.3, 45.0, 47.1, 52.0, 53.8, etc.

[0124] In some embodiments, when the proportion relationship of 15.0≤x≤53.8, 30.0≤y≤78.8 and 6.2≤z≤35.5 is satisfied and x+y+z=100, y can be any of the following values ​​or an interval consisting of any two of the following values: 30.0, 33.2, 35.0, 35.1, 40.0, 45.0, 49.5, 50.0, 50.1, 55.0, 60.0, 65.0, 70.0, 75.0, 78.8, etc.

[0125] In some embodiments, when the proportion relationship of 15.0≤x≤53.8, 30.0≤y≤78.8 and 6.2≤z≤35.5 is satisfied and x+y+z=100, z can be any of the following values ​​or an interval consisting of any two of the following values: 6.2, 10.0, 10.1, 13.0, 15.0, 20.0, 20.2, 25.0, 25.5, 30.0, 35.5, etc.

[0126] In some embodiments, based on any of the foregoing suitable embodiments, the Cr—Zr—N alloy coating satisfies the following two characteristics:

[0127] The X-ray diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;

[0128] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies

[0129] The means for structural characterization of the Cr-Zr-N alloy coating in the present invention can also be used to characterize the Cr-Zr-N alloy material provided by the present invention, and the Cr-Zr-N alloy material may not be limited to the coating form, but may be an independent raw material, such as an alloy sheet, an alloy plate, etc.

[0130] The Cr-Zr-N alloy coating provided by the present application is not clearly divided into the traditional perfect single crystal or fully amorphous state, but focuses on the close packing degree of atomic arrangement. Based on the specific atomic ratio of Cr, Zr and N, the close packing degree is closely related to the disorder of the atomic arrangement and the appropriate mismatch of the atomic size; the highly dense Cr-Zr-N alloy coating provided by the present invention has both high hardness and excellent corrosion resistance in performance, and structurally satisfies the requirements of having at least one broad peak (furthermore, there may be no sharp peak, that is, all are broad peaks) in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diagram and the radial intensity profile of the selected area electron diffraction pattern is There is at least one broad peak in the range (furthermore, there may be no sharp peaks, that is, all are broad peaks).

[0131] In the present invention, whether the constituent atoms of the alloy coating have a "highly disordered" state is evaluated by XRD technology. Specifically, the XRD diagram of the Cr-Zr-N alloy coating shows wide and gentle ridges, and these "wide and gentle ridges" are called "broad peaks" of the 2θ (°) diffraction peak. The length of the orderly arrangement of atoms can be obtained by using the Scherrer formula from the half-height width of the wide peak. The calculation method is: D = Kλ / (β·cosθ), where D is the length of the orderly arrangement of atoms (representing the grain size in crystalline materials), K is the Scherrer constant, λ is the wavelength of X-rays; β is the half-height width of the diffraction peak (referring to the width value at half the height of the diffraction peak, Full Width at Half Maximum, FWHM), and θ is the diffraction angle. It can be seen that the half-height width FWHM is inversely proportional to the length D of the orderly arrangement of atoms, and the shorter the length D of the orderly arrangement of atoms, the higher the disorder of the atomic distribution. Therefore, the half-width (FWHM) of the diffraction peak within a specific range in the XRD diagram can be used to reflect the degree of disordered distribution of atoms: the wider the half-width (FWHM), the shorter the length of the ordered arrangement of atoms, and the more disordered the overall atomic distribution; the aforementioned wide and gently raised "broad peak" can reflect the highly disordered distribution of atoms in the material as a whole.

[0132] Generally speaking, the higher the atomic order, the stronger the crystallinity, the easier it is to form large-sized grains over a long distance, the narrower the diffraction peak in the XRD diagram, and high crystallinity is often accompanied by sharp peaks. In the alloy coating of the present invention, the three atoms of Cr, Zr, and N can be highly disordered in the Cr-Zr-N alloy coating as a whole, so that it appears as a wide and gentle ridge (broad peak) in the XRD diagram of the Cr-Zr-N alloy coating, which is manifested as "at least one peak in the diffraction angle 2θ (°) range of 30° to 50° is a "broad peak".

[0133] In the present invention, unless otherwise specified, the "broad peak" in the XRD pattern can be defined as a half-height width satisfying ≥2°. The half-height width of the broad peak can further be ≥2.2°, further ≥2.23°, further ≥2.25°, further ≥2.3°, further ≥3°, further ≥3.5°, further ≥3.92°, further ≥4°, further ≥5°. The half-height width of any "broad peak" in the XRD graph can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​and less than or equal to 10°, and can also be selected from an interval consisting of any two of the following values: 2°, 2.23°, 2.25°, 2.5°, 3°, 3.5°, 3.52°, 3.92°, 4°, 4.5°, 5°, 5.5°, 5.56°, 6°, 6.5°, 7°, 7.5°, 8.42°, 8.5°, 9°, 9.5°, etc. As a non-limiting example, it can be selected from any of the following ranges: 2° to 10°, 2° to 9.5°, 2° to 9°, 2.2° to 8.5°, 2.20° to 8.45°, 2.23° to 8.42°, etc.

[0134] In the present invention, unless otherwise specified, a "sharp peak" in an X-ray diffraction (XRD) pattern refers to a diffraction peak with a half-height width < 2°.

[0135] In more detail, in the Cr-Zr-N alloy coating provided by the present application, the XRD pattern has peaks in the diffraction angle 2θ(°) range of 30° to 50°, and at least one of the diffraction peaks in the XRD spectrum is a broad peak. The special microstructural state in which at least one peak is a "broad peak" can be represented by "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" or "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°". The following method can be used to determine whether "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" is satisfied: in the XRD spectrum, if the half-width value of the 2θ(°) diffraction peak is ≥2°, it is judged as a "broad peak"; if the half-width value of the 2θ(°) diffraction peak is <2°, it is judged as a sharp peak. For a certain specified 2θ(°) position, it can be any of the three states of no peak, broad peak or sharp peak. In the X-ray diffraction (XRD) diagram, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious.

[0136] In the traditional Cr-Zr-N alloy coating with a high content of columnar crystals, the diffraction peak in the diffraction angle 2θ (°) range of 30° to 50° often appears as a sharp peak with a half-height width < 2°, and no broad peak appears.

[0137] In the present invention, conventional instruments and methods in the art can be used to obtain the XRD pattern of the alloy coating, for example, a German Bruker D8 Advance XRD diffractometer can be used.

[0138] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and at least one 2θ(°) diffraction peak in the range of 30° to 50° is a broad peak, and the half-width value of the broad peak can be referred to the examples in the context; taking the half-width of the broad peak ≥2.23° as an example, at least one 2θ(°) diffraction peak in the range of 30° to 50° satisfies ≥2.23°.

[0139] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has a broad peak within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of the broad peak can be found in the examples in the context.

[0140] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has two or more broad peaks within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height widths of these broad peaks can be independently referred to the examples in the context.

[0141] In some embodiments, in the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention, all 2θ(°) diffraction peaks within the diffraction angle 2θ(°) range of 30° to 50° are broad peaks, that is, there are no sharp peaks at this time, and the half-height widths of these broad peaks can be independently referred to the examples in the context.

[0142] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and the half-height width of the 2θ(°) diffraction peak in the range of 30° to 50° each independently satisfies ≥2°, further can each independently satisfy ≥2.2°, further can each independently satisfy ≥2.23°, further can each independently satisfy ≥2.25°, further can each independently satisfy ≥2.3°, further can each independently satisfy ≥3°, further can each independently satisfy ≥3.5°, further can each independently satisfy ≥4°, further can each independently satisfy ≥5°.

[0143] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has only one diffraction peak within the diffraction angle 2θ (°) range of 30° to 50°, and the diffraction peak is a broad peak.

[0144] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating is obtained by Cu target Kα radiation.

[0145] In the present invention, the following instruments and methods can be used to obtain the XRD pattern of the alloy coating: using a German BrukerD8 Advance XRD diffractometer, in θ-2θ mode, using Cu target Kα rays, a wavelength λ of 0.15406nm, the X-ray tube is controlled at 40kV and 40mA, the scanning range is 20° to 80°, and precise scanning measurement is performed with a step size of 0.01°.

[0146] The half-width value can be obtained by conventional analysis methods in the art (including but not limited to analysis software provided by the instrument supplier). For example, the step of obtaining the half-width value may include: firstly performing correction processing on the diffraction peak, which may include: smoothing, subtracting the background, removing the Kα2 line, subtracting the instrument broadening, etc., and fitting the diffraction peak with the Pseudo-Voigt function to obtain the half-width value of the diffraction peak.

[0147] The analysis software is not particularly limited. Without limitation, EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) can be used to process the spectrum data. For example, the following method can be used: first, a scale calibration is performed, and then the center of the diffraction ring transmission spot is determined, and then converted into an XRD spectrum (wherein the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak is deducted from the straight line background, and then fitted with a Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0148] Regarding the characterization of the degree of atomic density in alloy coatings, traditional XRD patterns cannot be used to characterize it well. This is because: when detecting physical vapor deposition (PVD) films or coatings at the atomic scale (such as diameter <3nm), the XRD method often has insufficient resolution due to the large wavelength of X-rays (>0.1nm), and is not suitable for PVD films or coatings with low order (such as grains or amorphous grains with a diameter <3nm).

[0149] In the present invention, whether the atoms constituting the coating have reached "sufficiently densely packed" is evaluated by the selected area electron diffraction pattern (Selected Area Electron Diffraction, SAED). The electron wave is selected because its wavelength is significantly smaller (<0.01nm), so the resolution is higher. Specifically, if there are only continuous diffraction rings with consistent brightness on the SEAD graph, and the diffraction rings are relatively wide, it indicates that the atoms in the coating are densely packed in a highly random mixed manner. In order to quantitatively characterize, the SAED spectrum can be converted into a characteristic atomic spacing (d)-radial intensity profile, wherein the characteristic atomic spacing (d) is the horizontal coordinate and the diffraction intensity is the vertical coordinate. If the diffraction rings in the SEAD are relatively wide, then correspondingly, the half-height width of the radial intensity profile is relatively wide, reflecting that the atomic arrangement in the alloy coating is densely packed.

[0150] In this application, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The three atoms with different diameters have a suitable atomic size mismatch, and under the condition of high random mixing, a fully dense structure can be formed. In the growth process of PVD film or alloy coating, the fully dense stacking of atoms in Cr-Zr-N alloy coating makes the alloy coating easy to grow densely, which can inhibit the formation and growth of columnar crystals originally caused by local ordering, and then make it difficult for continuous through-type pores to form in large quantities. Thus, the half-height width of the radial intensity profile can be used as the characteristic parameter of the fully dense structure of the alloy coating to reflect the dense packing of atoms in the alloy coating. The larger the value of the half-height width, the better the dense packing of atoms in the alloy coating. In short, the present invention adopts the half-height width of the radial intensity profile of SAED as the characteristic parameter of fully dense atomic stacking, which is in line with scientific principles and has scientificity.

[0151] When the half-height width of the radial intensity profile is greater than a certain threshold, the atoms in the coating can be fully densely packed. According to a large number of experimental explorations by the inventors, in the present invention, unless otherwise specified, the half-height width threshold for judging whether the atoms are fully densely packed in the SAED-radial intensity profile is determined as Half-height width When the atoms are fully packed together,

[0152] In the present invention, a transmission electron microscope (TEM) technique may be used to obtain a radial intensity profile of a characteristic atomic spacing (d) of an alloy coating sample.

[0153] In the present invention, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating can be recorded as a SAED-radial intensity profile, and can also be recorded as a characteristic atomic spacing-intensity quantitative spectrum of the selected area electron diffraction pattern (SAED pattern). The selected area electron diffraction pattern obtained by transmission electron microscopy can be recorded as a TEM selected area electron diffraction pattern, and can also be recorded as a TEM-SAED pattern. The SAED-radial intensity profile obtained by transmission electron microscopy can also be recorded as a TEM-SAED-radial intensity profile.

[0154] In the present invention, the alloy coating (including the Cr-Zr-N alloy coating of the present invention) can be obtained by using conventional instruments and methods in the art, and the corresponding radial intensity profile can be obtained according to the selected area electron diffraction pattern (SAED) of the alloy coating. It is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal coordinate and the unit being angstroms. The vertical axis represents the electron diffraction intensity.

[0155] In the present invention, unless otherwise specified, the half-height width of the diffraction peak in the radial intensity profile of the SAED pattern is It is judged as a broad peak; the half-height width of the diffraction peak For a specific characteristic interatomic distance, it can be any of the three states of no peak, sharp peak or broad peak. In the radial intensity profile, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious. Unless otherwise specified, the "broad peak" in the radial intensity profile of the selected area electron diffraction pattern (SAED pattern) refers to the half-height width The diffraction peak of the spectrum is referred to as the half-height width. diffraction peaks.

[0156] In the present invention, the radial intensity profile or SAED-radial intensity profile, unless otherwise specified, can be obtained using TEM technology.

[0157] In the present invention, unless otherwise specified, the “broad peak” in the radial intensity profile corresponding to the SAED pattern can be defined as the half-height width satisfying The half-width of the broad peak can be further Further, you can Further, you can Further, you can Further, you can

[0158] In the present invention, the following transmission electron microscopy (TEM) method can be used (but not limited to) to obtain the half-width at half maximum data in the radial intensity profile corresponding to the selected area electron diffraction pattern:

[0159] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0160] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) of Thermo Fisher Co., Ltd. of the United States was used with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain the selected area electron diffraction pattern (SAED) of the sample. Based on the selected area electron diffraction pattern (SAED) image, a radial intensity profile was obtained, and the half-height width value of the diffraction peak was obtained by using the integrated half-height width assignment.

[0161] According to the principle that the half-width of the diffraction peak in the radial intensity profile corresponds to the width of the diffraction ring in the selected area electron diffraction pattern (SAED) pattern, the selected area electron diffraction pattern (SAED) pattern of the alloy coating can be converted into the corresponding radial intensity profile.

[0162] Those skilled in the art know that the larger the width of the diffraction ring in the selected area electron diffraction pattern, the stronger the random mixing degree of the atoms, and the more densely packed the atoms are in the Cr-Zr-N alloy coating of the present invention; the half-width of the diffraction peak in the radial intensity profile is a quantitative indicator of the width of the diffraction ring, and the larger the half-width value, the more densely packed the atoms are.

[0163] In some embodiments, the selected area electron diffraction pattern (SAED) of the Cr-Zr-N alloy coating of the present invention is obtained using a transmission electron microscope (TEM) characterization technique, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0164] In some embodiments, in the radial intensity profile of the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention, has at least one half-width diffraction peaks.

[0165] In the radial strength cross-sectional diagram of the Cr-Zr-N alloy coating provided by the present invention, The half-height width of the diffraction peak in the range has an upper limit due to the atomic close packing limit. Non-limiting examples of the upper limit are as follows:

[0166] In the present invention, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​and less than or equal to the aforementioned upper limit value (such as ), and can also be independently selected from an interval consisting of any two of the following values:

[0167] As a non-limiting example, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be selected from any of the following ranges:

[0168]

[0169] etc.

[0170] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating, The half-height width of the diffraction peak in the range

[0171] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating of the present invention, The half-height width of the diffraction peak within the range can be independently any of the following values, can be independently greater than or equal to any of the following values, and can also be independently selected from an interval consisting of any two of the following values:

[0172] As a non-limiting example, any of the following ranges may be selected:

[0173] wait.

[0174] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There is one broad peak in the range, and its half-height width can be found in the examples in the context.

[0175] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There are 2 or more broad peaks in the range, and their half-height widths can be independently determined by referring to the examples in the context.

[0176] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is All diffraction peaks within the range are broad peaks, and the half-height width of all diffraction peaks meets See also context definition.

[0177] In some embodiments, the characteristic atomic spacing of the Cr-Zr-N alloy coating of the present invention is obtained using TEM diffraction data; wherein, the TEM diffraction test of the alloy coating is performed using an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0178] In some embodiments, the TEM test uses a mode with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain a selected area electron diffraction pattern (SAED) of the Cr—Zr—N alloy coating.

[0179] Regarding the internal mechanism analysis of the high hardness and excellent corrosion resistance of the Cr-Zr-N alloy coating provided by the present application, the inventors of the present application have found through a large number of experimental explorations that for the Cr-Zr-N alloy coating, when the following two conditions are met at the same time: (1) the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and (2) the radial intensity profile of the selected area electron diffraction pattern is The prepared Cr-Zr-N alloy coating has high hardness and excellent corrosion resistance. If only the XRD diffraction pattern has at least one broad peak in the range of 30° to 50° in the diffraction angle 2θ (°) and the radial intensity profile of the SAED pattern is If there is no broad peak in the range, the prepared Cr-Zr-N alloy coating may have poor corrosion resistance. For example, the corresponding aluminum alloy substrate sample may not pass the 24h or 48h salt spray corrosion test. The XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, while the diffraction angle 2θ(°) in the XRD diffraction pattern has no broad peak in the range of 30° to 50°, which may also lead to the poor corrosion resistance of the Cr-Zr-N alloy coating.

[0180] In some embodiments, based on any of the above suitable embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min It can be selected from 10nm to 50nm, d min It can also be any of the following thicknesses, or a range selected from any two of the following thicknesses: 10nm, 20nm, 25nm, 30nm, 40nm, 50nm, etc.; for example, the thickness of the Cr-Zr-N alloy coating can be 25nm~6μm, 30nm~6μm, 40nm~6μm, 50nm~6μm, 1.0μm~2.5μm, 1.0μm~2.0μm, etc.

[0181] By controlling the Cr-Zr-N alloy coating of the present invention to have a more appropriate thickness, the high hardness characteristics and / or corrosion resistance of the alloy protective coating can be better utilized. The thicker the Cr-Zr-N alloy coating, the more conducive it is to improving the hardness and / or corrosion resistance of the alloy coating. The Cr-Zr-N alloy coating provided by the present invention can have both high hardness characteristics and high corrosion resistance at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. Compared with traditional Zr-containing alloy coatings, at the same thickness, the Cr-Zr-N alloy coating of the present invention can provide a denser structure and can achieve better high hardness characteristics and corrosion resistance.

[0182] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 10 nm to 6 μm.

[0183] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 25 nm to 6 μm.

[0184] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 1 μm to 2.5 μm.

[0185] In addition, when the thickness of the alloy coating is relatively thin, the formed coated product can also present a silvery white metallic color, which is close to the metallic color of the substrate, which is conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0186] The Cr-Zr-N alloy coating provided in each embodiment of the present invention may be doped with other elements or may not be doped with other elements, and can be flexibly selected according to the additional functional requirements of the alloy material and / or the alloy coating. It can be understood that in the present invention, when doping elements are contained, the type and amount of doping elements are limited to not affecting the high hardness and corrosion resistance of the Cr-Zr-N alloy coating.

[0187] In the present invention, the chemical formula of the Cr-Zr-N alloy material contained in the Cr-Zr-N alloy coating can be expressed as (Cr x Zr y N z )M a , where x, y and z are each independently an atomic ratio and a positive number, M is a doping element, and a is an atomic ratio of the M element and is 0 or a positive number. During the nucleation process, N atoms can penetrate into the pores of large-sized Cr and Zr metal grains, achieving a better pore-filling effect, making the coating atoms more densely stacked, and also inhibiting the growth defects of the thin film columnar crystal structure, thereby improving the corrosion resistance of the coating.

[0188] When a is 0, the Cr-Zr-N alloy material does not contain doping elements, corresponding to the Cr-Zr-N ternary alloy material. When a>0, the Cr-Zr-N alloy material contains doping elements, wherein a / (x+y+z) is numerically equal to the relative atomic percentage of the doping elements relative to Cr, Zr, and N, and a / (x+y+z+a) is numerically equal to the atomic percentage of the doping elements in the Cr-Zr-N alloy material.

[0189] Unless otherwise specified, the Cr-Zr-N alloy material involved in each embodiment of the present invention mainly contains three elements: Cr, Zr and N. Furthermore, the sum of the atomic ratios of the three elements accounts for ≥95% of the sum of the atomic ratios of all elements in the Cr-Zr-N alloy material (corresponding to 0≤a / (x+y+z+a)≤0.05, such as 0≤a / (x+y+z)≤0.05), further such as ≥98% (corresponding to 0≤a / (x+y+z+a)≤0.02, such as 0≤a / (x+y+z)≤0.02), and further such as Cr-Zr-N ternary alloy material (at this time, a=0). By limiting the content of doping elements, the influence of doping elements on the highly disordered and sufficiently densely packed arrangement of atoms in the Cr-Zr-N alloy coating of the present application can be minimized, which is beneficial to reducing the elements required for doping or reducing the difficulty of doping, simplifying the preparation process, and promoting the coordinated deposition of Cr, Zr and N to form a denser coating, which is beneficial to achieving higher hardness and better corrosion resistance.

[0190] In some embodiments, a / (x+y+z)=0. At this time, the Cr-Zr-N ternary alloy material has a simple composition and is easier to prepare and control. The Cr-Zr-N ternary alloy coating formed at this time can obtain a dense structure and can achieve high hardness and high corrosion resistance.

[0191] In some embodiments, 0

[0192] In some embodiments, 0

[0193] ​​In some preferred embodiments, 0

[0194] In some embodiments, the doping element is a non-metallic element, a metallic element or a combination thereof, which can be flexibly selected according to the additional functional requirements of the Cr-Zr-N alloy coating. It is understood that in the present invention, when doping elements are contained, the type and doping amount of the doping elements are limited to being able to form the Cr-Zr-N alloy coating structure of the present invention without affecting the excellent high hardness and corrosion resistance.

[0195] Without limitation, the non-metallic element may include one or more of O, C, B, Si and Ar. Without limitation, the metal element may include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0196] ​It should be noted that in any embodiment of the context of the present application, the Cr-Zr-N alloy coating provided by the present application and the Cr-Zr-N alloy material involved allow the presence of inevitable impurities introduced during the preparation process. "Inevitable impurities" are not intentionally added impurities, and the main reason for their existence is that they are accidentally introduced during the preparation process; non-limiting examples of "inevitable impurities" include, for example, elements such as C and O present in the air, and may also come from components in raw materials or equipment. The atomic content of "inevitable impurities" in the Cr-Zr-N alloy coating is usually trace or micro, which can generally be ignored, such as less than 0.01% atomic content. Taking the technical solution of "Cr-Zr-N alloy coating is a Cr-Zr-N ternary alloy material composed of Cr, Zr and N elements" as an example, at this time, theoretically, the Cr-Zr-N alloy coating is composed of three elements: Cr, Zr and N, but trace or micro amounts of other elements other than Cr, Zr and N may be introduced during the preparation process, such as C, O, etc.

[0197] In one aspect of the present invention, there is further provided a Cr—Zr—N alloy material as defined in the first aspect of the present invention.

[0198] In a second aspect of the present invention, a coated product is provided, comprising a substrate 100 and the Cr-Zr-N alloy coating described in the first aspect of the present invention (i.e., the Cr-Zr-N alloy coating 300 of the present application); wherein the Cr-Zr-N alloy coating is located on at least one side of the substrate. The Cr-Zr-N alloy coating may be present in the protective coating of the coated product, giving the protective coating high hardness and excellent corrosion resistance.

[0199] The Cr-Zr-N alloy coating provided by the present invention can be located on one side or both sides of the substrate.

[0200] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material. Without limitation, the material type of the alloy may include one or more of a nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based. Without limitation, the single metal may be any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium. Without limitation, the inorganic non-metallic material may include one or more of ceramics and glass. Without limitation, the inorganic non-metallic material may include a silicon wafer.

[0201] Furthermore, the Cr-Zr-N alloy coating provided by the present invention can be applied to a variety of substrates, the materials of the substrates include but are not limited to alloys, elemental metals and other materials, and can also be used for other types of substrates such as inorganic non-metallic materials (such as silicon wafers, ceramics, glass).

[0202] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; optionally, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0203] In some embodiments, the surface material of the substrate is one of light alloys; further, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0204] In some embodiments, the surface material of the substrate is one of stainless steel alloys. Further, the stainless steel alloy can be any one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, etc.

[0205] In some embodiments, the coated article satisfies one or more of the following features:

[0206] The Cr-Zr-N alloy coating is in direct contact with the substrate (in this case, there is no transition layer) or a transition layer is provided. Further, the transition layer may be a single-layer structure or a multi-layer structure (that is, one or more structural layers may be formed between the Cr-Zr-N alloy coating provided by the present invention and the substrate);

[0207] The Cr-Zr-N alloy coating is located on the surface of the coated product or a surface layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate. Furthermore, the surface layer can be a single-layer structure or a multi-layer structure (that is, one or more structural layers can continue to be formed on the Cr-Zr-N alloy coating provided by the present invention).

[0208] In this application, unless otherwise specified, "transition layer" and "transition film layer" have the same meaning and can be used interchangeably. Both refer to a structural layer with transitional properties located between the substrate and the Cr-Zr-N alloy coating described in this application in a coated product, which can be a single-layer structure or a multi-layer structure.

[0209] In this application, unless otherwise specified, "surface layer" and "surface film layer" have the same meaning and can be used interchangeably. They both refer to the structural layer of the Cr-Zr-N alloy coating described in this application in the coated product, which is away from the substrate side and located on the surface of the product. It can be a single-layer structure or a multi-layer structure.

[0210] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is in direct contact with the substrate 100 (in this case, there is no transition layer).

[0211] In some implementations, a transition layer 200 is provided between the Cr—Zr—N alloy coating 300 and the substrate 100 of the present application.

[0212] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is located on the surface of the coated product.

[0213] In some implementations, a surface layer 400 is further provided on a side of the Cr—Zr—N alloy coating 300 of the present application away from the substrate 100 .

[0214] Figure 1 It is a schematic structural diagram of a coated product including the Cr—Zr—N alloy coating of the present application in one embodiment of the present invention, including a substrate 100 and the Cr—Zr—N alloy coating 300 of the present application.

[0215] Figure 2 Schematic diagrams of the structures of the coated products in several embodiments of the present invention: (A) includes a substrate 100, a transition layer 200 and a Cr-Zr-N alloy coating 300 of the present application; (B) includes a substrate 100, a transition layer 200, a Cr-Zr-N alloy coating 300 of the present application and a surface layer 400; (C) includes a substrate 100, a Cr-Zr-N alloy coating 300 of the present application and a surface layer 400.

[0216] In the coated product, the position of the Cr-Zr-N alloy coating provided by the present invention can be flexibly set, and it can directly contact the substrate or not directly contact the substrate. It can be used as a surface layer or be located between the surface layers of the substrate and other structures and serve as an intermediate film layer. The Cr-Zr-N alloy coating of the present invention at different positions can effectively resist scratches and scrapes while also providing excellent corrosion resistance.

[0217] When the Cr-Zr-N alloy coating of the present invention is located on the surface of the film-coated product (the Cr-Zr-N alloy coating of the present invention is used as the surface layer of the film-coated product at this time), the highly dense structure of the alloy coating can also be used to obtain better coating reflection characteristics, thereby providing the film-coated product with a surface with high brightness, so that the coating has both beautiful decoration and protective effects. When testing the chromaticity value of the alloy coating, the sample to be tested adopts a substrate material suitable for practical application, and the degree of improvement of the compactness and other properties of the substrate by the alloy coating is detected. The L value, a value and b value of the sample can be tested by a CM-3700A-U desktop spectrophotometer produced by Konica Japan, and the light receiving system selects the F2 light source, and the average value is taken after testing 6 matrix points for each sample. Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values. The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer takes the incident light as the surface of the sample to be tested, forming a reflection and obtaining a reflectance curve. The amplitude of the curve can reflect the density of the material, which can be specifically represented by the L value. For the same material, the higher its density, the larger the L value it displays.

[0218] According to the difference in the main components of the substrate, the coated product can be any one of a light alloy product, a stainless steel product, a single metal, an inorganic non-metal-based product (such as a ceramic-based product, a silicon-based product, a glass-based product), etc., indicating that the main components of the substrate are light alloy, stainless steel, single metal, etc., respectively. Without limitation, light alloy products may include but are not limited to aluminum alloy products, titanium alloy products, magnesium alloy products, etc. Without limitation, stainless steel products may include but are not limited to austenitic stainless steel, ferritic stainless steel, martensitic stainless steel. Without limitation, single metal products may include but are not limited to zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium, further such as copper, aluminum, iron, silver and chromium.

[0219] In a third aspect of the present invention, there is provided application of the Cr—Zr—N alloy coating according to the first aspect of the present invention.

[0220] The application fields of the Cr-Zr-N alloy coating described in the first aspect of the present invention include but are not limited to the application fields of traditional hard coatings, such as but not limited to 3C digital products, automotive parts or accessories, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace and other product or technical fields.

[0221] Examples of the hard coating and its applicable fields in the third aspect of the present application can also refer to the aforementioned first aspect.

[0222] In some embodiments, the application of the Cr-Zr-N alloy coating described in the first aspect of the present invention as at least a part of the hard coating, or the application of the coated product described in the second aspect of the present invention in the preparation of a product with a hard coating is provided. Furthermore, the hard coating is also a corrosion-resistant coating. As a non-limiting example, the product with a hard coating can be a structural part with high hardness requirements and easy wear in the fields of 3C digital products, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace, tool surface, etc.

[0223] The Cr-Zr-N alloy coating provided by the present invention can be used as at least a part of a hard coating, can be used as a protective coating of a single structure layer, can also be used as a layer of a multi-layer structure protective coating, can be used as a surface film layer, an intermediate film layer or a bottom film layer of a hard coating. The aforementioned coated product can be an intermediate product or a final product, and various products with a hard coating can be further prepared. The hard coating not only has high hardness characteristics, but can also provide excellent corrosion resistance as a corrosion-resistant coating.

[0224] The final product can be used or sold directly, while the intermediate product can be further processed or assembled with other components into new products.

[0225] In some embodiments, taking an aluminum alloy substrate as an example, a hard coating including the Cr-Zr-N alloy coating of the present application is formed on the surface of the aluminum alloy substrate, and the protection time in the salt spray corrosion test can be ≥24 hours, that is, it can pass the 24-hour test, and most embodiments can also pass the 48-hour test; the ASTM B117 salt spray test method can be used, and the following examples can also be referred to. Under the same test conditions, the protection time of traditional hard coatings in the salt spray corrosion test is generally difficult to reach 8 hours.

[0226] When the Cr-Zr-N alloy coating of the present invention is used for protection, it can also provide better hardness and corrosion resistance than traditional protective layers at the same thickness. Therefore, it can have both high hardness characteristics and excellent corrosion resistance at a thinner thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs.

[0227] In the fourth aspect of the present invention, a method for preparing a Cr-Zr-N alloy coating comprises the following steps: using vapor deposition technology to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of a substrate according to a preset atomic ratio to form the Cr-Zr-N alloy coating described in the first aspect of the present invention.

[0228] The preparation method of the Cr-Zr-N alloy coating provided by the invention is simple, easy to operate, green and environmentally friendly, and also has the advantages of being quantifiable, highly efficient and highly repeatable, and is suitable for industrial application.

[0229] The definition of the substrate may be incorporated into the second aspect of the invention.

[0230] In some embodiments, the vapor deposition technique is a physical vapor deposition technique. Further, the physical vapor deposition technique can be implemented by one or more of the following methods: vacuum evaporation, sputtering, arc plasma plating, ion plating, and molecular beam epitaxy.

[0231] In one embodiment, the physical vapor deposition method is magnetron sputtering coating.

[0232] In some embodiments, sputtering coating (such as magnetron sputtering coating) technology is used to deposit the constituent elements of the Cr—Zr—N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio.

[0233] See also Figure 3 The device shown. Figure 3The device shown includes a vacuum chamber 1, a sample stage 2, a DC anode 3, a chromium target 4 and a zirconium target 5; wherein the chromium target 4 is a chromium target with radio frequency assisted DC cathode power supply, and the zirconium target 5 is a zirconium target with radio frequency assisted DC cathode power supply. The figure is not drawn in a 1:1 ratio, and the relative sizes of the components are drawn in the figure only as examples to facilitate the understanding of the present invention, but are not necessarily drawn in true proportions, and the proportions in the figure do not constitute a limitation of the present invention. The Cr-Zr-N alloy coating of the present invention can be formed by reactive sputtering with a N2-containing gas (such as an Ar / N2 mixed gas) in the vacuum chamber 1.

[0234] In some embodiments, the preparation method of the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas containing argon and a nitrogen-containing gas, using one or more targets including chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating. The nitrogen-containing gas may be, but is not limited to, nitrogen. At this time, the gas ratio of argon and nitrogen in the mixed gas may be (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the Cr-Zr-N alloy coating of the present invention can be further adjusted.

[0235] The target material may include one or more of a chromium target, a zirconium target, and an alloy target. The alloy target includes at least two metal elements in the Cr-Zr-N alloy coating. The atomic ratio of the metal elements in the alloy target may be the same as or close to the atomic ratio of the corresponding metal elements in the Cr-Zr-N alloy coating. In some embodiments, the alloy target is a chromium-zirconium-based alloy target, wherein the chromium-zirconium-based alloy target includes at least chromium and zirconium, such as a CrZr alloy target, a CrZrN alloy target, and the like. In some embodiments, the atomic ratio of Cr and Zr in a chromium-zirconium-based alloy target (such as a CrZr alloy target) is 65%:35%. In some embodiments, the atomic ratio of Cr and Zr in a chromium-zirconium-based alloy target (such as a CrZr alloy target) is 55%:45%. In some embodiments, the alloy target includes all metal elements in the Cr-Zr-N alloy coating. Examples of alloy targets can be found in Examples 2 and 11 below.

[0236] In the present invention, unless otherwise specified, a "chromium-zirconium-based alloy target" includes at least chromium and zirconium, and may include or exclude other elements. When other elements are included, it is understood that the chemical composition of the target material should generally be within the preset chemical formula (Cr x Zr y N z )M aFor example, the chromium-zirconium-based alloy target may be a chromium-zirconium-nitrogen alloy target (ie, a CrZrN alloy target) composed of three elements: chromium, zirconium, and nitrogen.

[0237] In some embodiments, a chromium-zirconium alloy target is used, which can be replaced Figure 3 Medium chromium target 4, installed on Figure 3 The location of Zhongyuan chromium target 4.

[0238] In some embodiments, the preparation method of the Cr-Zr-N alloy coating, taking a sputtering coating method (such as a magnetron sputtering coating) method as an example, comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using a chromium target and a zirconium target or a chromium-zirconium alloy target (i.e., a CrZr alloy target), sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.

[0239] In some embodiments, before the step of "sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate", the following step is also included: cleaning the substrate. The method for cleaning the substrate can adopt a conventional cleaning method in the technical field (including but not limited to the field of decorative plating).

[0240] In some embodiments, the cleaning treatment of the substrate includes the following steps: placing the substrate in water for ultrasonic cleaning for 10-15 minutes, vacuum drying the cleaned substrate for 15-20 minutes, and placing the substrate on a sample stage of a sputtering coating (such as magnetron sputtering coating) device after drying. The sample stage may be a rotatable sample stage.

[0241] In one embodiment, the cleaning process of the substrate includes the following steps: placing the substrate in deionized water (DI water) for ultrasonic cleaning for 10-15 minutes, placing the cleaned substrate in a vacuum baking oven for baking for 15-20 minutes, and placing the substrate on a rotatable sample table in a vacuum chamber after drying.

[0242] In some embodiments, after the step of "cleaning the substrate", and before the step of "sputtering and depositing constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate", the following step is also included: forming a transition layer on at least a portion of the surface of the cleaned substrate, for example, the constituent elements of the transition layer can be deposited on at least a portion of the surface of the cleaned substrate.

[0243] In some embodiments, after the Cr—Zr—N alloy coating of the present invention is formed on one side of the substrate, further deposition may be performed to form a surface layer, and the surface layer may be a single-layer structure or a multi-layer structure.

[0244] In some embodiments, the temperature of sputtering deposition is 30°C to 330°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 330°C, etc.

[0245] In some embodiments, the total gas pressure of the mixed gas comprising argon gas and nitrogen-containing gas is 0.3 Pa to 1.2 Pa; for example, 0.3 Pa, 0.5 Pa, 0.8 Pa, 1 Pa, 1.2 Pa, etc.

[0246] In some embodiments, sputtering is performed by radio frequency assisted direct current sputtering, which can further improve the performance of the alloy coating formed by sputtering deposition compared to other preparation methods.

[0247] In some embodiments, the target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 .

[0248] In some embodiments, the target material includes a zirconium target, and the power density of the zirconium target is 0.8 W / cm 2 ~7.9W / cm 2 .

[0249] In some embodiments, the target material includes a chromium target and a zirconium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 , and the power density of the zirconium target is 0.8W / cm 2 ~7.9W / cm 2 .

[0250] In some embodiments, the target material comprises a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4 W / cm 2 ~6W / cm 2 .

[0251] In some embodiments, the bias voltage of the substrate is -150 V to -20 V; for example, -150 V, -120 V, -100 V, -90 V, -80 V, -60 V, -50 V, -40 V, -30 V, -20 V, etc.

[0252] In some embodiments, the gas flow rate of the nitrogen-containing gas may be 8 sccm to 52 sccm, such as 8 sccm, 10 sccm, 20 sccm, 25 sccm, 30 sccm, 40 sccm, 50 sccm, 52 sccm, etc. Further, the nitrogen-containing gas is nitrogen gas.

[0253] In some embodiments, the sputtering deposition time is 10 min to 150 min, for example, 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 100 min, 120 min, etc. The thickness of the Cr-Zr-N alloy coating of the present invention can be controlled by adjusting the deposition time. As the deposition time increases, the thickness of the Cr-Zr-N alloy coating increases.

[0254] In some embodiments, the background vacuum of the vacuum chamber used is ≤5.0×10 -4 Pa. This pressure setting can ensure the collision between the sputtered particles and the gas molecules, and can also reduce the entry of impurities into the gas molecules during the deposition process, so as to improve the corrosion resistance, purity and bonding strength of the Cr-Zr-N alloy coating of the present invention.

[0255] It can be understood that argon gas and nitrogen-containing gas can be introduced into the vacuum chamber through a single path or mixed through a mixing cylinder and then enter the chamber, thereby reducing the impurity content of the Cr-Zr-N alloy coating of the present invention and improving its performance.

[0256] In some embodiments, “using sputtering coating (such as magnetron sputtering coating) technology to load the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio” includes the following steps: introducing a mixed gas containing argon and nitrogen-containing gas into the vacuum chamber 1, maintaining the pressure in the vacuum chamber 1 at 0.3Pa to 1.2Pa (such as 0.5Pa to 0.8Pa), turning on the bias voltage and setting it to -150V to -20V, and setting the power density of the chromium target 4 to 1.3W / cm 2 ~6.7W / cm 2 , the power density of zirconium target 5 is set to 0.8 W / cm 2 ~7.9W / cm 2 , a Cr-Zr-N alloy coating is deposited on at least a portion of the surface of the substrate after cleaning; further, the Cr-Zr-N alloy coating with different film thicknesses can be obtained by controlling the film forming time.

[0257] In a fifth aspect of the present invention, a Cr-Zr-N alloy material is provided, which may be as defined in the first aspect of the present invention, or may be a Cr-Zr-N alloy material in any embodiment in the context. As mentioned above, the Cr-Zr-N alloy material has a suitable atomic size mismatch and a special atomic ratio, and can form the Cr-Zr-N alloy coating of the present invention with a high random mixing degree of "highly disordered and fully densely packed".

[0258] In some embodiments, the Cr-Zr-N alloy material satisfies the following two characteristics:

[0259] The X-ray diffraction pattern of the Cr-Zr-N alloy material has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;

[0260] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies

[0261]

[0262] Furthermore, the XRD test results of the Cr-Zr-N alloy material and the radial intensity profile results corresponding to the selected area electron diffraction pattern can also refer to the description of the radial intensity profile corresponding to the X-ray diffraction pattern and the selected area electron diffraction pattern in the Cr-Zr-N alloy coating in this article, and the corresponding optional and preferred methods can also be applied to the Cr-Zr-N alloy material.

[0263] Some specific embodiments are provided below.

[0264] The embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are preferably referred to the guidance provided in the present invention, and can also be based on the experimental manual or normal conditions in this area, can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0265] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0266] Test method:

[0267] 1. Hardness test of alloy coating

[0268] When testing the hardness of alloy coatings, the sample to be tested adopts a substrate suitable for actual application.

[0269] The surface material of the "substrate suitable for practical application" may include, but is not limited to: aluminum alloy, stainless steel, copper sheet.

[0270] In the following examples, unless otherwise specified, when testing the hardness of the alloy coating, aluminum alloy and stainless steel are used as the substrate, and the alloy coating is deposited on the aluminum alloy and stainless steel using preset preparation parameters to obtain the test sample for testing the hardness of the alloy coating. This is mainly due to the following considerations: During the nanoindentation test, when the probe penetrates the test sample, a strong pressure is formed. At this time, the substrate is required to have a certain toughness. If a brittle silicon wafer is used, cracking may occur during the test, resulting in inaccurate test results. Alloy materials are more suitable as the substrate to be tested for nanoindentation testing due to their excellent toughness. At the same time, the use of alloy materials as the substrate to measure nanohardness is more universal in the field of nanohardness parameter characterization in the field of coated areas.

[0271] The hardness of each film or coating was tested using a nanoindenter model NHT3 produced by Anton-Paar, Austria. It was equipped with a tetrahedral Berkvich indenter, and the indentation depth was set to 100 nm. The load changed with the indentation depth. Five matrix points were tested for each sample and the average value was taken.

[0272] 2. Salt spray corrosion resistance test of alloy coating

[0273] When the salt spray corrosion resistance test of the alloy coating is carried out, the sample to be tested is a substrate suitable for practical application, and the improvement degree of the corrosion resistance of the substrate by the alloy coating is detected. The surface material of the "substrate suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.

[0274] The ASTM B117 salt spray test standard is adopted, the pH value of the solution is 6.5-7.2, and the chemical composition of the solution is: sodium chloride (NaCl), deionized water and sodium hydroxide (NaOH).

[0275] 12 hours can be used as a sub-cycle of the salt spray corrosion resistance test.

[0276] The test cycle of alloy coatings prepared on substrates of different materials can be different, for example:

[0277] The test cycle for samples containing aluminum alloy matrix is ​​48h or 24h;

[0278] The test cycle of stainless steel substrate samples is 144h or 96h;

[0279] The test cycle of the copper sheet substrate sample is 12h.

[0280] The standard for "passing (OK)" salt spray corrosion resistance test is: after the sample is tested, there is no corrosion, no discoloration, and no rust on the appearance.

[0281] The standard for "failure (NG)" in the salt spray corrosion test is: after the sample is tested, corrosion, discoloration or rust is found on the surface.

[0282] 3. Morphology and composition test analysis of alloy coating

[0283] The samples to be tested all use silicon wafers as substrates.

[0284] Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) testing methods

[0285] Morphology analysis: A scanning electron microscope (Regulus 8230, manufactured by Hitachi) was used.

[0286] Composition analysis: An energy dispersive X-ray spectrometer (EDX) attached to a Regulus 8230 scanning electron microscope produced by Hitachi was used, and the relative intensities of all elements were corrected by the ZAF method.

[0287] Test parameters: the electron acceleration voltage is 15 kilovolts, the beam current is 10 microamperes, the sample magnification is 200 times, and each sample is tested at 10 points and the average is taken.

[0288] 4. X-ray diffraction (XRD) test of alloy coating

[0289] When conducting XRD testing of alloy coatings, silicon wafers were used as substrates.

[0290] 4.1. Calculation of the half-width of the diffraction peak in the XRD pattern

[0291] A German Bruker D8 Advance XRD diffractometer was used in the θ-2θ mode with Cu target Kα rays, a wavelength λ of 0.15406 nm, the X-ray tube controlled at 40 kV and 40 mA, a scanning range of 20° to 80°, and precise scanning measurements with a step size of 0.01°.

[0292] The steps for obtaining the half-width value are as follows: first, the diffraction peak is corrected, including: smoothing, background subtraction, removal of Kα2 line, subtraction of instrument broadening, etc., and the half-width value of the diffraction peak is obtained after fitting the diffraction peak with the Pseudo-Voigt function.

[0293] The EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) was used to process the spectrum data: first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and then converted into an XRD spectrum (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak was deducted from the straight line background, and then fitted with the Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0294] 4.2. Determine whether the XRD pattern of the alloy coating forms a broad peak

[0295] Method for judging whether there are broad peaks (sharp peaks) in the diffraction angle range of 2θ (°) from 30° to 50° in the XRD diffraction pattern: in the XRD spectrum, if the half-height width of the 2θ (°) diffraction peak is ≥2°, it is judged as a broad peak; if the half-height width of the 2θ (°) diffraction peak is <2°, it is judged as a sharp peak.

[0296] For a given 2θ(°) position, it can be any of the three states: no peak, sharp peak or broad peak.

[0297] 5. TEM test

[0298] When conducting TEM tests on alloy coatings, silicon wafers were used as substrates.

[0299] 5.1. The half-width at half maximum of the diffraction ring of the TEM diffraction pattern is obtained by the following method:

[0300] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0301] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) produced by Thermo Fisher Scientific Inc., USA, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm, was used to obtain the selected area electron diffraction pattern (SAED) of the sample.

[0302] Acquisition of radial intensity profile: The SAED spectrum data obtained above were processed using EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney): first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and finally, it was converted into a radial intensity profile (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers), with the characteristic atomic spacing as the horizontal axis and the diffraction intensity as the vertical axis.

[0303] The steps for obtaining the half-width value are as follows: subtract a straight line from the diffraction peak, and then fit it with the Voigt function to obtain the half-width value of the corresponding diffraction peak.

[0304] 5.2. Determine the radial intensity profile of the TEM selected area electron diffraction pattern Method to determine whether there is a broad peak within the range: the half-height width of the diffraction peak corresponding to the characteristic atomic spacing It is judged as a broad peak; the half-height width of the diffraction peak corresponding to the characteristic atomic spacing is For a specific characteristic interatomic distance, it can be any of the three states: no peak, sharp peak or broad peak.

[0305] 6. Chroma value test of alloy coating

[0306] When testing the chromaticity value of the alloy coating, the sample to be tested uses a substrate that is suitable for practical application, and detects the degree of improvement of the density and other properties of the substrate by the alloy coating. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.

[0307] The L value, a value and b value of the samples were tested using a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The F2 light source was selected as the light receiving system. Six matrix points were tested for each sample and the average value was taken.

[0308] Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values.

[0309] The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer reflects the incident light on the surface of the sample to be tested, and a reflectance curve is obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. For the same material, the higher its density, the larger the L value it displays.

[0310] In the following examples, DI water means deionized water.

[0311] The stainless steel sheets, aluminum alloy sheets and silicon sheets in the following embodiments and comparative examples are made of the same material.

[0312] In the following examples, the target material was sputtered by RF-assisted DC sputtering.

[0313] In the following examples, the reference to “there is only one broad peak” in the XRD diagram and the SAED-radial intensity profile diagram, unless otherwise specified, means there is only one characteristic peak, and the peak is a broad peak.

[0314] Example 1.

[0315] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 53.8 Zr 40.0 N 6.2 .

[0316] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0317] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0318] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 8 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.2 W / cm 2 , the power density of the Zr target was set to 3.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the obtained film thickness is 2500nm.

[0319] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0320] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr53.8 Zr 40.0 N 6.2 .

[0321] The hardness of the aluminum alloy substrate sample was 16.1GPa, and the hardness of the stainless steel substrate sample was 18.3GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0322] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 4 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 5 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-width of 8.42° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0323] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 77.02, a: 0.52, b: 4.99; the chroma value of the stainless steel substrate sample tested is L: 79.36, a: 0.40, b: 4.49, which is silvery white in color.

[0324] Example 2.

[0325] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 34.5 Zr 30.0 N 35.5 , the preparation method is as follows:

[0326] In this embodiment, the target material is a chromium-zirconium alloy target. Figure 3 The Zhongyuan chromium target 4 was replaced with a CrZr alloy target with an atomic percentage ratio of 55%:45%.

[0327] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, keep at room temperature (about 30°C) for 15 minutes.

[0328] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0329] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the CrZr alloy target, introduce Ar and N2 gas, set the N2 gas flow rate to 42 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the CrZr alloy target to 5.0 W / cm 2 , depositing a Cr-Zr-N alloy coating, and by controlling the film forming time, the resulting film thickness is made to be 2000nm.

[0330] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0331] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 34.5 Zr 30.0 N 35.5 .

[0332] The hardness of the aluminum alloy substrate sample was 21.7GPa, and the hardness of the stainless steel substrate sample was 22.1GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0333] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 6 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 7 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 3.52° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0334] Chroma value test results: The chroma value of the aluminum alloy substrate sample test is L: 74.20, a: 0.55, b: 7.68; the chroma value of the stainless steel substrate sample test is L: 77.26, a: 0.42, b: 7.11, which is silvery white in color.

[0335] Example 3.

[0336] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 15.0 Zr 78.8 N 6.2 , the preparation method is as follows:

[0337] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0338] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0339] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 8 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 1.3 W / cm 2 , the power density of the Zr target was set to 7.9 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2500nm.

[0340] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0341] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 15.0 Zr 78.8 N 6.2 .

[0342] The hardness of the aluminum alloy substrate sample tested was 20.6GPa, and the hardness of the stainless steel substrate sample tested was 22.8GPa. In the salt spray corrosion resistance test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0343] The SEM cross-section of the test sample was characterized. The SEM image, TEM-SAED image and radial strength profile of the cross-section morphology can be found in Figure 8 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 3.92° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0344] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 74.29, a: 0.53, b: 6.38; the chroma value of the stainless steel substrate sample tested is L: 75.65, a: 0.47, b: 6.31, showing a bright silver-white color.

[0345] Example 4.

[0346] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 15.0 Zr 49.5 N 35.5 , the preparation method is as follows:

[0347] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heated to 150°C, kept constant for 15 minutes;

[0348] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0349] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 42 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 1.3 W / cm 2 , the power density of the Zr target was set to 5 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2200nm.

[0350] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0351] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 15.0 Zr 49.5 N 35.5 .

[0352] The hardness of the aluminum alloy substrate sample was 21.2GPa, and the hardness of the stainless steel substrate sample was 22.6GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0353] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Fig. 9 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Fig.10 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 2.23° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0354] Chroma value test results: The chroma value of the aluminum alloy substrate sample test is L: 75.25, a: 0.52, b: 6.48; the chroma value of the stainless steel substrate sample test is L: 76.95, a: 0.41, b: 6.04, showing a bright silver-white color.

[0355] Example 5.

[0356] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 29.7 Zr 50.1 N 20.2 , the preparation method is as follows:

[0357] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0358] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0359] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 24 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 2.6 W / cm 2 , the power density of the Zr target was set to 5 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2500nm.

[0360] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0361] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 29.7 Zr 50.1 N 20.2 .

[0362] The hardness of the aluminum alloy substrate sample was 19.5GPa, and the hardness of the stainless steel substrate sample was 21.7GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0363] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Fig.11, XRD diffraction pattern can be found at Fig.12 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern is a broad peak in the range of 30°~50°, that is, the half-height width of the diffraction angle 2θ(°) in the XRD diffraction pattern in the range of 30°~50° is ≥2°, and there is only one broad peak with a half-height width of 5.66° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.

[0364] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 76.13, a: 0.52, b: 5.88; the chroma value of the stainless steel substrate sample tested is L: 78.01, a: 0.42, b: 5.07, showing a bright silver-white color.

[0365] Example 6.

[0366] In this example, a double-layer film structure is attached to the substrate surface, including a chemical composition of Cr 15.0 Zr 78.8 N 6.2 The double-layer film structure is denoted as Cr-Zr-N / TiN. At this time, the substrate surface is attached with a multi-layer film structure, wherein the Cr-Zr-N alloy coating provided by the present application is used as an intermediate layer, located between the substrate and the surface layer. The preparation method is as follows:

[0367] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0368] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0369] Depositing the Cr-Zr-N alloy coating of the present invention: turning on the sample stage rotating frame, setting the rotation speed to 6 revolutions per minute, adjusting the distance from the sample stage to the target surface to 8 cm, using a radio frequency assisted DC power supply to draw power to the Cr target and the Zr target, introducing Ar and N2 gas, setting the N2 gas flow rate to 8 sccm, setting the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintaining the furnace pressure at 0.7 Pa, turning on the bias voltage, setting it to -100 V, and setting the power density of the Cr target to 1.3 W / cm2 , the power density of the Zr target was set to 7.9 W / cm 2 , depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0370] Deposition surface layer: replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2 , TiN coating is deposited, and by controlling the film formation time, the obtained film thickness is 100nm.

[0371] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0372] After component analysis, the component is Cr 15.0 Zr 78.8 N 6.2 The alloy coating is provided with a TiN coating (as a surface layer) on the surface.

[0373] The hardness of the aluminum alloy substrate sample tested was 12.2GPa, and the hardness of the stainless steel substrate sample tested was 14.5GPa. In the salt spray corrosion resistance test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0374] The SEM cross-section test of the test sample showed that the Cr-Zr-N alloy coating had a dense structure.

[0375] Chroma value test results: The chroma value of the aluminum alloy substrate sample test is L: 55.75, a: 6.65, b: 12.92, the chroma value of the stainless steel substrate sample test is L: 56.23, a: 6.82, b: 13.21, and it is golden in color.

[0376] Example 7.

[0377] In this example, a three-layer film structure is attached to the surface of the substrate, which includes a transition layer (as a bottom coating), a Cr-Zr-N alloy coating containing a Cr-Zr-N alloy material, and a surface layer located on the surface. The three-layer film structure is recorded as Cr / Cr-Zr-N / TiN, wherein the transition layer is a Cr layer, and the chemical composition of the Cr-Zr-N alloy coating of the present application is Cr.15.0 Zr 78.8 N 6.2 , the chemical composition of the surface layer is TiN. The preparation method is as follows:

[0378] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0379] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0380] Deposition of bottom coating (transition layer): Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target, introduce Ar, set the Ar gas volume to 42 sccm, maintain the furnace pressure at 0.5 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , deposit a Cr base coating, and by controlling the film formation time, the resulting film thickness is 300nm.

[0381] Deposition of the Cr-Zr-N alloy coating (intermediate coating) of the present application: Turn on the sample stage turret, set the rotation speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the Cr target and the Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 8 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 1.3 W / cm 2 , the power density of the Zr target was set to 7.9 W / cm 2 , depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0382] Deposition surface layer: replace the Zr target in the furnace with a Ti target, turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2 , depositing TiN coating, by controlling the film forming time, the obtained film thickness is 100nm;

[0383] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0384] According to the composition analysis, there are three layers of film structure on the surface of the substrate, and the chemical composition is Cr (transition layer), Cr 15.0 Zr 78.8 N 6.2 (Cr-Zr-N alloy coating of the present application) and TiN (surface layer), the three-layer film structure is Cr / Cr-Zr-N / TiN.

[0385] The hardness of the aluminum alloy substrate sample was 13.8GPa, and the hardness of the stainless steel substrate sample was 15.4GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0386] The SEM cross-section test of the test sample showed that the Cr-Zr-N alloy coating had a dense structure.

[0387] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 53.49, a: 7.07, b: 13.81; the chroma value of the stainless steel substrate sample tested is L: 55.73, a: 7.35, b: 14.50, which is golden in color.

[0388] Example 8.

[0389] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 15.0 Zr 78.8 N 6.2 , the preparation method is as follows:

[0390] Pretreatment: The copper and silicon wafer samples with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven, and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0391] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0392] Depositing the Cr-Zr-N alloy coating of the present invention: turning on the sample stage rotating frame, setting the rotation speed to 6 revolutions per minute, adjusting the distance from the sample stage to the target surface to 8 cm, using a radio frequency assisted DC power supply to draw power to the Cr target and the Zr target, introducing Ar and N2 gas, setting the N2 gas flow rate to 8 sccm, setting the gas volume to maintain the Ar: N2 gas volume ratio of 6:1, maintaining the furnace pressure at 0.7 Pa, turning on the bias voltage, setting it to -100 V, and setting the power density of the Cr target to 1.3 W / cm 2 , the power density of the Zr target was set to 7.9 W / cm 2 , depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0393] The samples using copper sheets as the substrate were subjected to salt spray corrosion resistance test, hardness test and chromaticity value test, and the samples using silicon sheets as the substrate were subjected to SEM and composition analysis, XRD analysis and TEM test.

[0394] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 15.0 Zr 78.8 N 6.2 The hardness of the copper substrate sample tested was 8.9GPa. In the salt spray corrosion test, the copper substrate sample can pass the 12h test and has certain protective properties.

[0395] The SEM test results show that the alloy coating has a dense structure and no penetrating column cracks are observed.

[0396] The chromaticity values ​​of the copper substrate sample tested were L: 74.78, a: 0.56, b: 6.58, showing a bright silver-white color.

[0397] Example 9. Cr-Zr-N alloy coating thickness is about 50nm

[0398] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 29.7 Zr 50.1 N 20.2 , the only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 50nm.

[0399] The hardness of the aluminum alloy substrate sample tested was 9.1GPa, and the hardness of the stainless steel substrate sample tested was 9.8GPa. In the salt spray corrosion resistance test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0400] Chroma value test results: The chroma value of the aluminum alloy substrate sample tested is L: 77.23, a: 0.51, b: 5.98, and the chroma value of the stainless steel substrate sample tested is L: 78.81, a: 0.41, b: 5.27, showing bright silver-white color.

[0401] Example 10. Cr-Zr-N alloy coating thickness is about 6 μm

[0402] The same method as in Example 5 was used, and the chemical composition of the Cr-Zr-N alloy coating was Cr 29.7 Zr 50.1 N 20.2 The only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 6000nm.

[0403] The hardness of the aluminum alloy substrate sample tested was 23.8GPa, and the hardness of the stainless steel substrate sample tested was 25.2GPa. In the salt spray corrosion resistance test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0404] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 75.23, a: 0.55, b: 6.08; the chroma value of the stainless steel substrate sample tested is L: 76.81, a: 0.42, b: 5.57, showing bright silver-white color.

[0405] Example 11. Containing doping elements

[0406] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating containing doping elements is Cr 34.5 Zr 30.0 N 30.5 C5, at this time, the sum of the atomic ratios of Cr, Zr and N is normalized to 100, and the atomic ratios of Cr, Zr and N are about 36.32:31.58:32.11, and the atomic percentage of the doping element C in the Cr-Zr-N alloy coating is 5%. The preparation method is as follows:

[0407] In this embodiment, the target material is a chromium-zirconium alloy target. Figure 3 The original chromium target (original Cr target) at the position of the middle chromium target 4 is replaced with a CrZr alloy target with an atomic percentage ratio of 55%:45%.

[0408] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0409] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0410] Deposition of the Cr-Zr-N alloy coating of the present application: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the CrZr alloy target, introduce Ar, C2H2 and N2 gases, set the N2 gas flow rate to 35 sccm, the C2H2 gas flow rate to 6 sccm, set the gas volume to maintain the Ar: (C2H2 + N2) gas volume ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the CrZr alloy target to 4.5 W / cm 2 , depositing the Cr-Zr-N alloy coating of the present application (specifically a carbon-doped Cr-Zr-N alloy coating), and by controlling the film forming time, the obtained film thickness is 2500nm.

[0411] Stainless steel sheets and aluminum alloy sheets were used as the substrate samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the substrate samples for SEM and composition analysis, XRD analysis and TEM test.

[0412] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 34.5 Zr 30.0 N 30.5 C5.

[0413] The hardness of the aluminum alloy substrate sample was 21.2GPa, and the hardness of the stainless steel substrate sample was 21.8GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 48h test, and the stainless steel substrate sample passed the 144h test, showing excellent protection characteristics.

[0414] The diffraction angle 2θ(°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.

[0415] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 73.80, a: 0.59, b: 6.78; the chroma value of the stainless steel substrate sample tested is L: 76.16, a: 0.42, b: 6.71, showing bright silver-white color.

[0416] According to the experimental exploration results of the inventors, when other non-metallic doping elements (such as Si, B, O, etc.) or metal doping elements (such as Al) are used, when the atomic ratio of the doping elements is appropriate (such as 4at%, 2at%), it can also provide higher hardness and excellent corrosion resistance. In some embodiments, in the salt spray corrosion resistance test experiment, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test. It can also have at least one broad peak in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diffraction pattern, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.

[0417] "at%" means atomic percent, by number.

[0418] Example 12.

[0419] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 53.8 Zr 30 N 16.2 The element composition does not conform to the following combination formula: 64.5-y≤x≤93.8-y and 15.0≤x≤1.93y-23.4.

[0420] The preparation method is as follows:

[0421] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0422] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0423] Depositing the Cr-Zr-N alloy coating of the present invention: turning on the sample stage rotating frame, setting the rotation speed to 6 revolutions per minute, adjusting the distance from the sample stage to the target surface to 8 cm, using a radio frequency assisted DC power supply to draw power to the Cr target and the Zr target, introducing Ar and N2 gas, setting the N2 gas flow rate to 18 sccm, setting the gas volume to maintain the Ar: N2 gas volume ratio of 3:1, maintaining the furnace pressure at 0.7 Pa, turning on the bias voltage, setting it to -100 V, and setting the power density of the Cr target to 4.5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2, depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0424] Stainless steel sheets and aluminum alloy sheets were used as the substrate samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the substrate samples for SEM and composition analysis, XRD analysis and TEM test.

[0425] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 53.8 Zr 30 N 16.2 .

[0426] The hardness of the aluminum alloy substrate sample was 11.1 GPa, and the hardness of the stainless steel substrate sample was 12.3 GPa. In the salt spray corrosion test, the aluminum alloy substrate sample passed the 24h test (failed the 48h test), and the stainless steel substrate sample passed the 96h test (failed the 144h test), which showed good but not excellent corrosion resistance.

[0427] The diffraction angle 2θ(°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range.

[0428] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 77.52, a: 0.68, b: 4.12; the chroma value of the stainless steel substrate sample tested is L: 79.34, a: 0.51, b: 3.74, which is silvery white in color.

[0429] In addition, the inventors of the present application have found through a large number of experimental explorations that for the Cr-Zr-N alloy coating of the present application, when the following two conditions are met at the same time: (1) the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and (2) the radial intensity profile of the TEM selected area electron diffraction pattern is The prepared Cr-Zr-N alloy coating has high hardness and excellent corrosion resistance. If only the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50° and the radial intensity profile in the TEM-SAED pattern is If there is no broad peak in the range, the prepared Cr-Zr-N alloy coating may have poor corrosion resistance. For example, the corresponding aluminum alloy substrate sample may not pass the 24h salt spray corrosion test. The XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, while the diffraction angle 2θ (°) in the XRD diffraction pattern has no broad peak in the range of 30° to 50°, which may also lead to poor corrosion resistance of the Cr-Zr-N alloy coating. Please refer to the following Comparative Example 4.

[0430] Comparative Example 1.

[0431] In this comparative example, the chemical composition of the alloy coating is Cr 88.9 Zr 11.1 The preparation method is as follows:

[0432] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0433] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0434] Deposition of Cr-Zr alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar gas, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage and set it to -100 V, and set the power density of the Cr target to 6.7 W / cm 2 , the power density of the Zr target was set to 0.8 W / cm 2 , a Cr-Zr alloy coating was deposited, and by controlling the film forming time, the obtained film thickness was 1900nm.

[0435] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity value tests. Silicon wafers were used as substrate samples for SEM and composition analysis tests.

[0436] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 88.9 Zr 11.1 .

[0437] The hardness of the aluminum alloy substrate sample was 18.5GPa, and the hardness of the stainless steel substrate sample was 19.6GPa. In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), indicating poor protection characteristics.

[0438] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.13 The SEM test results show that the alloy coating film has crystal defects, a loose structure, and obvious gaps.

[0439] Chroma value test results: the chroma value of the aluminum alloy substrate sample tested is L: 83.21, a: -0.21, b: 0.88, and the chroma value of the stainless steel substrate sample tested is L: 85.05, a: -0.25, b: 0.79, which is silvery white in color.

[0440] Comparative Example 2.

[0441] In this comparative example, the chemical composition of the alloy coating is Cr 37.8 Zr 16.2 N 46 , the preparation method is as follows:

[0442] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0443] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0444] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 52 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.9 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 3.5 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0445] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0446] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 37.8 Zr 16.2 N 46.

[0447] The hardness of the aluminum alloy substrate sample was 16.6GPa, and the hardness of the stainless steel substrate sample was 18.1GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), indicating poor protection properties.

[0448] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.14 The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found at Fig.15 . The SEM test results show that the alloy coating film has a loose structure and obvious penetrating column cracks. The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50°, and both are sharp peaks (2θ peaks with a half-height width value of <2°). Among them, the half-height widths of the two peaks in the range of 30° to 50° are 0.66° and 1.24° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there are two peaks.

[0449] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 61.87, a: 0.57, b: 4.45; the chroma value of the stainless steel substrate sample tested is L: 67.38, a: 0.49, b: 4.29. The color is dull and does not have a metallic color.

[0450] Comparative Example 3.

[0451] In this comparative example, the thin film structure is TiN, and the chemical composition of the alloy coating is TiN.

[0452] To prepare the coating of this comparative example, the Zr target in the furnace body was replaced with a Ti target, and the preparation method was as follows:

[0453] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0454] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0455] Deposition of TiN coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a DC power supply to energize the Ti target, introduce Ar and N2 gas, set the N2 gas flow rate to 10 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.5 Pa, turn on the bias, set it to -100 V, and set the power density of the Ti target to 5 W / cm 2 , a TiN alloy coating is deposited, and by controlling the film formation time, the obtained film thickness is 200nm.

[0456] Stainless steel sheets and aluminum alloy sheets were used as substrate samples for salt spray corrosion resistance tests, hardness tests and chromaticity tests.

[0457] The composition analysis showed that the alloy coating on the substrate surface was composed of TiN.

[0458] The hardness of the aluminum alloy substrate sample was 3.8GPa, and the hardness of the stainless steel substrate sample was 4.3GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h).

[0459] Chroma value test results: The chroma value of the aluminum alloy substrate sample tested is L: 57.95, a: 6.45, b: 13.95; the chroma value of the stainless steel substrate sample tested is L: 59.33, a: 6.92, b: 13.91, which is golden in color.

[0460] Comparative Example 4.

[0461] In this comparative example, the chemical composition of the alloy coating is Cr 39.6 Zr 19.4 N 41 , the preparation method is as follows:

[0462] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0463] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0464] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 45 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.6 W / cm 2 , the power density of the Zr target was set to 2.2 W / cm 2 , depositing a Cr-Zr-N alloy coating. By controlling the film forming time, the thickness of the obtained alloy coating film is 1400nm.

[0465] Stainless steel sheets and aluminum alloy sheets were used as the matrix samples for salt spray corrosion resistance test, hardness test and color value test. Silicon wafers were used as the matrix samples for SEM and composition analysis, XRD analysis and TEM test.

[0466] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 39.6 Zr 19.4 N 41 .

[0467] The hardness of the aluminum alloy substrate sample was 15.4GPa, and the hardness of the stainless steel substrate sample was 17.2GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0468] The SEM test results show that the alloy coating film has crystal defects, the structure is not dense, and there are obvious penetrating column gaps. The XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile of the alloy coating can be found at Fig.16 (A), (B) and (C) in the figure. The XRD test results show that there are two peaks in the diffraction angle 2θ (°) in the XRD diffraction pattern within the range of 30° to 50°, and both are sharp peaks (2θ peaks with half-height width values ​​< 2°). Among them, the half-height widths of the two peaks within the range of 35° to 40° are 1.87° and 1.02° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there is one peak.

[0469] Chroma test results: The chroma value of the aluminum alloy substrate sample tested is L: 64.71, a: 0.58, b: 4.15; the chroma value of the stainless steel substrate sample tested is L: 66.38, a: 0.49, b: 4.27, which is silvery white in color.

[0470] Comparative Example 5. Alloy coating thickness 50nm

[0471] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 50nm.

[0472] The hardness of the aluminum alloy substrate sample was 9.1GPa, and the hardness of the stainless steel substrate sample was 9.8GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0473] Comparative Example 6. Alloy coating thickness 1000nm

[0474] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 1000nm.

[0475] The hardness of the aluminum alloy substrate sample was 16.5GPa, and the hardness of the stainless steel substrate sample was 17.9GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0476] Comparative Example 7: Alloy coating thickness 2500nm

[0477] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 2500nm.

[0478] The hardness of the aluminum alloy substrate sample was 20.5GPa, and the hardness of the stainless steel substrate sample was 21.1GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0479] Comparative Example 8: Alloy coating thickness 6000nm

[0480] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 6000nm.

[0481] The hardness of the aluminum alloy substrate sample was 22.1GPa, and the hardness of the stainless steel substrate sample was 23.7GPa. In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0482] Comparative Examples 9-11. No protective coating

[0483] Aluminum alloy bare chips, stainless steel bare chips and copper bare chips were respectively subjected to salt spray corrosion resistance tests. The results showed that obvious corrosion occurred within 12 hours.

[0484] Result analysis:

[0485] The Cr, Zr and N elements in the Cr-Zr-N alloy coating provided by the present invention satisfy a certain atomic ratio and are rich in zirconium.

[0486] The Cr-Zr-N alloy coating (Examples 1-12) provided by the present invention can be used as the protective coating itself or as a part of the protective coating, and can provide a higher hardness and have excellent corrosion resistance.

[0487] According to the salt spray corrosion resistance test results, the Cr-Zr-N alloy coatings (Examples 1-12) provided by the present invention can bring excellent corrosion resistance to the substrate; among them, Examples 1-5 and 8-12 are single-layer film structures, and the Cr-Zr-N alloy coatings provided by the present invention directly provide surface protection for the substrate; Example 6 is a double-layer film structure, and the Cr-Zr-N alloy coating provided by the present invention is used as a lower protective layer, and a surface layer (TiN coating) is also attached to the surface of the side of the Cr-Zr-N alloy coating away from the substrate. The coating is used as a surface decorative coating (located on the upper layer); the Cr-Zr-N alloy coating in Example 7 is a three-layer thin film structure, which includes a transition layer (as a bottom coating), a Cr-Zr-N alloy coating and a TiN coating located on the surface in sequence from the substrate surface; the Cr-Zr-N alloy coating in Example 11 contains a certain atomic percentage of doping elements (≤5at%); the element composition in Example 12 does not conform to the following combination formula: "64.5-y≤x≤93.8-y and 15.0≤x≤1.93y-23.4".

[0488] Examples 1-7, 9-11 all use aluminum alloy substrates and stainless steel substrates, and the Cr-Zr-N alloy coating can pass the 48h salt spray corrosion test on the aluminum alloy surface and the 144h salt spray corrosion test on the stainless steel surface. Example 8 uses a copper substrate, and the copper substrate (compared to aluminum alloy, copper is a more active alloy) can pass the 12h salt spray corrosion test. In Example 12, the Cr-Zr-N alloy coating can pass the 24h salt spray corrosion test on the aluminum alloy surface (but not the 48h test), and can pass the 96h salt spray corrosion test on the stainless steel surface (but not the 144h test).

[0489] The alloy coating provided by the present invention can be independently used as a single-layer film, or it can be located in a multi-layer composite film, for example, it can be used as one layer, that is, it can be used as a surface layer (exposed), it can also be used as a bottom coating (contacting the substrate), or it can be used as an intermediate layer (located between the bottom coating and the surface layer).

[0490] According to the results of XRD test and TEM selected area electron diffraction test, the Cr-Zr-N alloy coating (Examples 1-12) provided by the present invention has at least one broad peak (furthermore, all are broad peaks, and the half-height width is ≥2°) in the diffraction angle 2θ (°) in the XRD diffraction pattern within the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least one broad peak in the range (further, all are broad peaks, and the half-height width is ≥2°). The Cr-Zr-N alloy coatings of the present application all have a "highly disordered and fully densely packed" atomic arrangement, which is consistent with the highly dense structure in the SEM morphology characterization results.

[0491] In addition, when the Cr-Zr-N alloy coating provided by the present application is located on the surface of the protective coating (Examples 1-5, 8-12), it can also provide a higher brightness value for the corresponding coated product.

[0492] The bare substrate chips of Comparative Examples 9-11, without a protective coating, were not resistant to salt spray corrosion and suffered obvious corrosion within 12 hours.

[0493] The alloy coating film of Comparative Example 1 lacks N element, the alloy coating films of Comparative Example 2 and Comparative Example 4 have a high content of N element, and Comparative Example 3 does not have a Cr-Zr-N alloy coating (Comparative Example 3 has a TiN coating). The results show that Comparative Examples 1-4 all failed (NG) in the corrosion resistance test.

[0494] For the alloy coatings of different thicknesses in Comparative Examples 5-8, their hardness and corrosion resistance are significantly inferior to those of the Cr-Zr-N alloy coating of the present invention of the same thickness. Among them, even if Comparative Example 8 adopts a thickness of up to 6000nm (6 microns), its hardness is relatively high, but its corrosion resistance is still relatively poor. The reasons may be speculated to be: the film structure is not dense, and there are gaps, such as through-column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail; although increasing the thickness of the coating can increase the hardness of the coating, the structural defects still exist. The Cr-Zr-N alloy coating provided by the present invention can have both high hardness characteristics and excellent corrosion resistance at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the thickness of the alloy coating is relatively thin, the formed coated product can also present a silver-white metallic color, which is close to the metallic color of the substrate, which is conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0495] The technical features of the above-mentioned embodiments and examples can be combined in any appropriate manner. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0496] The above embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of protection of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. In addition, it should be understood that after reading the above teaching content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solution provided by the present invention through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the content of the attached claims, and the description and drawings can be used to explain the content of the claims.

Claims

1. A zirconium-rich Cr-Zr-N alloy coating, characterized in that: The Cr-Zr-N alloy coating contains a Cr-Zr-N alloy material, the chemical formula of which is (Cr x Zr y N z )M a , M is a doping element, wherein x, y, z and a are each independently an atomic ratio, 15.0≤x≤53.8, 30.0≤y≤78.8, 6.2≤z≤35.5, and 0≤a / (x+y+z+a)≤0.

05.

2. The Cr-Zr-N alloy coating according to claim 1, characterized in that: 64.5-y≤x≤93.8-y and 15.0≤x≤1.93y-23.

4.

3. The Cr-Zr-N alloy coating according to claim 1, characterized in that: 15.0≤x≤53.8, 33.7≤y≤78.8 and 6.2≤z<28.

0.

4. The Cr-Zr-N alloy coating according to claim 3, characterized in that: 72-y<x≤93.8-y and 15.0≤x<2.5y-44.

6.

5. The Cr-Zr-N alloy coating according to any one of claims 1 to 4, characterized in that: The sum of x, y, and z is 100.

6. The Cr-Zr-N alloy coating according to any one of claims 1 to 5, characterized in that: The Cr-Zr-N alloy coating meets the following two characteristics: The X-ray diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°; In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material or the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of At least within the range 7. The Cr-Zr-N alloy coating according to any one of claims 1 to 6, characterized in that: The thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10nm to 50nm.

8. The Cr-Zr-N alloy coating according to claim 7, characterized in that: d min It is 10nm, 20nm, 25nm, 30nm, 40nm or 50nm.

9. The Cr-Zr-N alloy coating according to any one of claims 1 to 6, characterized in that: The doping element is a non-metallic element, a metallic element or a combination thereof; The non-metallic elements include one or more of O, C, B, Si and Ar; The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

10. The Cr-Zr-N alloy coating according to any one of claims 1 to 9, characterized in that: 0≤a / (x+y+z+a)≤0.

02.

11. A coated product, characterized in that: It comprises a substrate and the Cr—Zr—N alloy coating according to any one of claims 1 to 11; wherein the Cr—Zr—N alloy coating is located on at least one side of the substrate.

12. The coated product according to claim 11, characterized in that: The surface material of the substrate is one of alloy, elemental metal and inorganic non-metallic material; The material type of the alloy includes one or more of nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based; The elemental metal is any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium; The inorganic non-metallic material includes one or more of ceramics and glass.

13. The coated product according to claim 12, characterized in that: The surface material of the substrate is one of the light alloys or one of the stainless steel alloys; The light alloy includes one or more of a titanium alloy, an aluminum alloy and a magnesium alloy.

14. The coated product according to claim 11, characterized in that: Satisfy one or more of the following characteristics: The Cr-Zr-N alloy coating is in direct contact with the substrate or is provided with a transition layer; The Cr-Zr-N alloy coating is located on the surface of the coated product or a surface layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate, and the surface layer is a single-layer structure or a multi-layer structure.

15. Use of the Cr-Zr-N alloy coating according to any one of claims 1 to 10 as at least a part of a hard coating layer, or use of the coated product according to claims 11 to 14 in the preparation of a product having a hard coating layer.

16. The use according to claim 15, characterized in that The hard coating is also a corrosion-resistant coating.

17. A method for preparing a Cr-Zr-N alloy coating, characterized in that: The method comprises the following steps: using vapor deposition technology to deposit the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate according to a preset atomic ratio, so as to form the Cr-Zr-N alloy coating according to any one of claims 1 to 10.

18. The preparation method according to claim 17, characterized in that: The preparation method of the Cr-Zr-N alloy coating comprises the following steps: under the condition of introducing a mixed gas comprising argon and a nitrogen-containing gas, using one or more target materials comprising chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating.

19. The preparation method according to claim 18, characterized in that: Satisfy one or more of the following characteristics: The temperature of sputtering deposition is 30℃~330℃; The total gas pressure of the mixed gas containing argon gas and nitrogen-containing gas is 0.3Pa to 1.2Pa; The target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 ; The target material includes a zirconium target, and the power density of the zirconium target is 0.8 W / cm 2 ~7.9W / cm 2 ; The target material includes an alloy target, and the alloy target includes at least two metal elements in the Cr-Zr-N alloy coating; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 ; The bias voltage of the substrate is -150V to -20V; The sputtering deposition time is 10min to 150min; The nitrogen-containing gas is nitrogen gas, and the gas flow rate of the nitrogen gas is 8 sccm to 52 sccm; The nitrogen-containing gas is nitrogen, and the gas volume ratio of argon and nitrogen in the mixed gas is (2-6):

1.

20. A Cr-Zr-N alloy material, characterized in that: The Cr—Zr—N alloy material is as defined in any one of claims 1-6, 9-10.

Citation Information

Patent Citations

  • Nitride hard film applied to surface of hot forging die and preparation method of nitride hard film

    CN114807850A

Cited By

  • Cr-ti-n alloy film, cr-ti-n alloy coating, alloy film product and use

    WO2025261349A1